Slurry composition for electrode film, electrode film, electrode for battery, and nonaqueous electrolyte secondary battery
The slurry composition for electrode films, utilizing carbon nanotubes and a nitrile group-containing polymer with a low molecular weight acidic compound, addresses dispersibility and stability issues, enhancing the conductivity and performance of non-aqueous electrolyte secondary batteries.
Patent Information
- Application Number
- JP2024188394
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2041-12-27
AI Technical Summary
Existing methods for dispersing carbon nanotubes in electrode films for non-aqueous electrolyte secondary batteries face challenges with poor dispersibility and stability, leading to decreased conductivity and increased electrode resistance, which affects the battery's output and cycle life.
A slurry composition for electrode films is developed using carbon nanotubes, a polymer with a nitrile group-containing structural unit, and a low molecular weight acidic compound, which is added at a specific timing to prevent gelation of fluoropolymers and enhance dispersibility and stability, resulting in improved conductivity and reduced electrode resistance.
The solution provides a slurry composition with enhanced dispersibility and stability, leading to improved output and cycle life of non-aqueous electrolyte secondary batteries.
Smart Images

Figure 2025010223000001_ABST
Abstract
Description
[Technical field]
[0001] An embodiment of the present invention relates to a method for producing a slurry composition for an electrode membrane, a method for producing an electrode membrane, a method for producing an electrode for a battery, and a method for producing a nonaqueous electrolyte secondary battery. [Background technology]
[0002] Lithium ion secondary batteries, which are typical non-aqueous electrolyte secondary batteries, are widely used as batteries for electric vehicles, portable devices, etc. As electric vehicles and portable devices become more powerful, there is an increasing demand year by year for lithium ion secondary batteries with high capacity, high output, and small size and light weight.
[0003] Since the capacity of a non-aqueous electrolyte secondary battery depends heavily on the main materials, the positive electrode active material and the negative electrode active material, various materials for use in these electrode active materials have been actively researched. However, the charge capacity when using electrode active materials in practical use has reached a level close to the theoretical value, and improvement is close to the limit. Therefore, since the charge capacity can be simply increased by increasing the filling amount of the electrode active material in the electrode film, attempts have been made to reduce the amount of conductive material and binder resin added, which do not directly contribute to the charge capacity.
[0004] The conductive material plays a role in forming a conductive path inside the electrode film and connecting between particles of the electrode active material, and it is required that the conductive path and connection are not easily broken by the expansion and contraction of the electrode film. In order to maintain the conductive path and connection with a small amount of additive, it is effective to form an efficient conductive network by using nanocarbon with a large specific surface area, especially carbon nanotubes (CNTs), as the conductive material. However, since carbon nanotubes with a large specific surface area have a strong cohesive force, there is a problem that it is difficult to disperse the carbon nanotubes well in the electrode film slurry and / or the electrode film.
[0005] In light of this background, many methods have been proposed in which a conductive material dispersion is prepared using various dispersants, and a slurry composition for an electrode film is produced via the conductive material dispersion (see, for example, Patent Documents 1 to 5). Patent Document 6 also proposes that a slurry for a secondary battery positive electrode is produced by a specific manufacturing process using a specific binder, thereby enabling the formation of a good conductive network between conductive materials. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2005-162877 A [Patent Document 2] JP 2014-193986 A [Patent Document 3] Special Publication No. 2018-522803 [Patent Document 4] JP 2015-128012 A [Patent Document 5] Korean Patent No. 10-1831562 [Patent Document 6] Patent No. 6413242 Summary of the Invention [Problem to be solved by the invention]
[0007] Patent Documents 1 and 2 propose using a polymer such as polyvinylpyrrolidone or polyvinyl alcohol as a dispersant to disperse carbon nanotubes in a solvent in advance to improve the initial characteristics and cycle life of a battery. However, although polyvinylpyrrolidone or polyvinyl alcohol can produce a carbon nanotube dispersion liquid in a good dispersed state, the dispersion state may become poor during the process of forming an electrode film, resulting in a decrease in electrical conductivity.
[0008] Patent Documents 3 and 4 propose conductive material dispersions using hydrogenated nitrile rubber as a dispersant. However, these hydrogenated nitrile rubbers have poor dispersibility, and therefore may not be able to form a good conductive network sufficiently. In addition, since the solution of hydrogenated nitrile rubber has high viscosity, it may take a long time to produce a conductive material dispersion, or the conductive material dispersion may have poor fluidity and be difficult to handle, which makes it difficult to put the dispersion into practical use industrially.
[0009] Patent Document 5 proposes a carbon nanotube dispersion in which the dispersibility is improved by adding aminoethanol or the like to hydrogenated nitrile rubber. In this CNT dispersion, it is believed that the action of the dispersant is improved by changing the polarity of the solvent. However, the resulting dispersion has a high viscosity and is still insufficient to form a good conductive network. Patent documents 1 to 5 discuss improving the initial dispersibility of the conductive material dispersion by specifying the type of dispersant, but do not fully consider the phenomenon in which the dispersibility and stability of carbon nanotubes decrease at the stage of preparing a composite slurry by adding an active material and a binder resin to the conductive material dispersion.
[0010] In a specific example of Patent Document 6, polyvinylidene fluoride is added to conductive paste 1 containing a hydrogenated product of a polymer containing conjugated diene monomer units, (meth)acrylic acid ester monomer units, and nitrile group-containing monomer units, acetylene black, and N-methyl-2-pyrrolidone to obtain conductive paste 2, and a positive electrode active material is further added to produce a positive electrode slurry. In contrast to the acetylene black used in this specific example, high aspect ratio carbon nanotubes exhibit excellent conductivity when finely dispersed in an electrode film, but there is a problem that carbon nanotubes tend to aggregate and therefore tend to have low dispersibility in the positive electrode slurry.
[0011] An object of one embodiment of the present invention is to provide a slurry composition for an electrode film having good dispersibility and good stability. Another object of one embodiment of the present invention is to provide an electrode film and a battery electrode that can improve the output and cycle life of a non-aqueous electrolyte secondary battery, and a non-aqueous electrolyte secondary battery having high output and good cycle life. [Means for solving the problem]
[0012] The present inventors have conducted extensive research and found that when the electrode membrane slurry composition contains carbon nanotubes (A) and an active material (C) in the presence of a polymer (B) containing a nitrile group-containing structural unit and a fluoropolymer (F), the electrode membrane slurry composition is unstable over time, causing an increase in electrode resistance. One of the factors that causes this stability over time is that the fluoropolymer (F) contained in the electrode membrane slurry composition gels due to its basicity. In order to suppress the gelation of the fluoropolymer (F), a low molecular weight acidic compound can be added to the electrode membrane slurry composition. The inventors focused on the fact that the timing of adding a low molecular weight acidic compound in a manufacturing method of a slurry composition for an electrode membrane affects the dispersibility and stability of carbon nanotubes in the slurry composition for an electrode membrane, and prepared a carbon nanotube dispersion liquid containing carbon nanotubes (A) and a polymer (B) containing a nitrile group-containing structural unit, and a slurry precursor for an electrode membrane containing an active material (D), a low molecular weight acidic compound (E) and a fluoropolymer (F), and mixed the carbon nanotube dispersion liquid with the slurry precursor for an electrode membrane, thereby making it possible to suppress gelation of the fluoropolymer (F) in the slurry composition for an electrode membrane and to obtain good dispersibility and stability of carbon nanotubes. In a method for producing a slurry composition for an electrode film, in which the low molecular weight acidic compound is added in any order by continuously mixing carbon nanotubes (A), a polymer (B) containing a nitrile group-containing structural unit, an active material (D), a low molecular weight acidic compound (E) and a fluoropolymer (F) in a solvent, the viscosity of the mixed composition may increase at the timing when the carbon nanotubes (A) and the low molecular weight acidic compound (E) are mixed, and further, aggregation of the carbon nanotubes (A) may occur. This is considered to be because, in the mixed composition, when the low molecular weight acidic compound (E) is directly added to a composition containing the carbon nanotubes (A) and the polymer (B) containing a nitrile group-containing structural unit, the polymer (B) containing a nitrile group-containing structural unit aggregates, causing a decrease in the dispersibility and stability of the carbon nanotubes (A).Furthermore, the electrode film and the battery electrode obtained by using the electrode film slurry composition obtained according to the manufacturing method of the present embodiment have good electrical conductivity and low electrode resistance, and the nonaqueous electrolyte secondary battery obtained by using this electrode film and battery electrode can improve the rate characteristics and cycle characteristics of the battery.
[0013] Some aspects of the invention are as follows. <1> A method for producing a slurry composition for an electrode membrane, comprising: preparing a carbon nanotube dispersion liquid containing carbon nanotubes (A), a polymer (B) containing a nitrile group-containing structural unit, and an amide-based organic solvent (C); and preparing a slurry precursor for an electrode membrane containing an active material (D), a low molecular weight acidic compound (E) having a molecular weight of less than 10,000, a fluorine-based polymer (F), and an amide-based organic solvent (C'), and mixing the carbon nanotube dispersion liquid and the slurry precursor for an electrode membrane.
[0014] <2> In the polymer (B) containing a nitrile group-containing structural unit, the content of the nitrile group-containing structural unit is 15% by mass or more and 50% by mass or less based on the mass of the polymer (B). <1> A method for producing a slurry composition for an electrode membrane according to claim 1. <3> The polymer (B) containing a nitrile group-containing structural unit has a weight average molecular weight of 5,000 or more and 500,000 or less. <1> or <2> A method for producing a slurry composition for an electrode membrane according to claim 1. <4> In the carbon nanotube dispersion, the carbon nanotube concentration x (mass%) and the complex elastic modulus y (Pa) of the carbon nanotube dispersion at 25° C. and a frequency of 1 Hz as determined by dynamic viscoelasticity measurement satisfy the relationships of the following formulas (1), (2), and (3): <1> from <3> 13. A method for producing a slurry composition for an electrode membrane according to claim 12. y<17x (1) y<120 (2) 0.1≦x≦10 (3)
[0015] <5> the above <1> from <4> 13. A method for producing an electrode membrane, comprising: preparing a slurry composition for an electrode membrane by the production method according to any one of claims 1 to 12; and producing an electrode membrane by using the slurry composition for an electrode membrane. <6> the above <1> from <4> 13. A method for producing an electrode for a battery, comprising: preparing a slurry composition for an electrode film by the production method according to any one of claims 1 to 12; and producing an electrode film on a current collector using the slurry composition for an electrode film. <7> A method for producing a non-aqueous electrolyte secondary battery including a negative electrode, a positive electrode, and an electrolyte, the step of producing either the negative electrode or the positive electrode comprising the steps of: <1> from <4> 13. A method for producing a nonaqueous electrolyte secondary battery, comprising: preparing a slurry composition for an electrode film by the production method according to any one of claims 1 to 12; and producing an electrode film on a current collector using the slurry composition for an electrode film. Effect of the Invention
[0016] According to one embodiment of the present invention, it is possible to provide a slurry composition for an electrode film having good dispersibility and good stability. Furthermore, according to one embodiment of the present invention, it is possible to provide an electrode film and a battery electrode that can improve the output and cycle life of a non-aqueous electrolyte secondary battery, and a non-aqueous electrolyte secondary battery having high output and good cycle life. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a graph showing the relationship between the CNT concentration (mass %) in a CNT dispersion and the complex modulus [G*] (Pa) determined by dynamic viscoelasticity measurement. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, a slurry composition for an electrode film, an electrode film, a battery electrode, a nonaqueous electrolyte secondary battery, etc., which are one embodiment of the present invention, will be described in detail. The present invention is not limited to the following embodiment, and the present invention also includes embodiments that are implemented within the scope of the present invention.
[0019] <Method for producing slurry composition for electrode membrane> The method for producing a slurry composition for an electrode membrane of this embodiment is characterized by comprising preparing a carbon nanotube dispersion liquid containing carbon nanotubes (A), a polymer (B) containing a nitrile group-containing structural unit, and an amide-based organic solvent (C), and a slurry precursor for an electrode membrane containing an electrode active material (D), a low molecular weight acidic compound (E) having a molecular weight of less than 10,000, a fluoropolymer (F), and an amide-based organic solvent (C'), and mixing the carbon nanotube dispersion liquid and the slurry precursor for an electrode membrane.
[0020] In this specification, carbon nanotubes may be referred to as "CNT". In addition, in this specification, carbon nanotube dispersion may be simply referred to as "dispersion". In addition, N-methyl-2-pyrrolidone may be referred to as "NMP". In this specification, polymer (B) containing a nitrile group-containing structural unit may be simply referred to as "polymer (B)".
[0021] <Carbon nanotube dispersion liquid> The carbon nanotube dispersion contains carbon nanotubes (A), a polymer (B) containing a nitrile group-containing structural unit, and an amide-based organic solvent (C).
[0022] The carbon nanotubes (A) are contained as a conductive material in the carbon nanotube dispersion. In addition to the carbon nanotubes, the carbon nanotube dispersion may optionally contain other conductive materials. Examples of the other conductive materials include metal powders such as gold, silver, copper, silver-plated copper powder, silver-copper composite powder, silver-copper alloy, amorphous copper, nickel, chromium, palladium, rhodium, ruthenium, indium, silicon, aluminum, tungsten, malbutene, and platinum, inorganic powders coated with these metals, powders of metal oxides such as silver oxide, indium oxide, tin oxide, zinc oxide, and ruthenium oxide, inorganic powders coated with these metal oxides, and carbon materials such as carbon black and graphite. The other conductive materials may be used alone or in combination of two or more. When using other conductive materials, carbon black is preferred from the viewpoint of the adsorption performance of the dispersant.
[0023] Carbon nanotubes are formed by rolling planar graphite into a cylindrical shape, and may be either single-walled carbon nanotubes or multi-walled carbon nanotubes, or a combination of these. Single-walled carbon nanotubes have a structure in which one layer of graphite is rolled. Multi-walled carbon nanotubes have a structure in which two or more layers of graphite are rolled. The sidewall of the carbon nanotube does not have to have a graphite structure. For example, carbon nanotubes having sidewalls with an amorphous structure are also carbon nanotubes in this specification. The carbon nanotube may be a carbon nanotube that has been subjected to a surface treatment. The carbon nanotube may also be a carbon nanotube derivative to which a functional group, typically a carboxyl group, has been added.
[0024] The shape of the carbon nanotube is not limited. The shape of the carbon nanotube includes various shapes including needle-like, cylindrical tube-like, fishbone-like (fishbone or cup stack type), trump-like (platelet) and coil-like. The shape of the carbon nanotube is preferably needle-like or cylindrical tube-like. The carbon nanotube may be a single shape or a combination of two or more shapes.
[0025] Examples of the form of carbon nanotubes include graphite whiskers, filamentous carbon, graphite fibers, ultrafine carbon tubes, carbon tubes, carbon fibrils, carbon microtubes, and carbon nanofibers. The carbon nanotubes may have a single form or a combination of two or more of these forms.
[0026] The BET specific surface area of carbon nanotubes is 20 to 1,000 m 2 / g, and 30 to 800m 2 It is more preferable that the molecular weight is / g.
[0027] The fiber length of the carbon nanotubes is preferably 50 nm or more and 5000 nm or less, and may be 80 nm or more and 2000 nm or less, or may be 100 nm or more and 1000 nm or less. Carbon nanotubes with a fiber length of 100 nm or more can further increase the electrical conductivity and toughness. Furthermore, carbon nanotubes with a fiber length of 1000 nm or less can suppress the occurrence of aggregation even if defibration progresses in the dispersion treatment, and can further prevent the viscosity of the dispersion from increasing.
[0028] Carbon nanotubes are evaluated by the G / D ratio (peak ratio of G-band to D-band). The G / D ratio of carbon nanotubes is determined by Raman spectroscopy. Carbon nanotubes have a peak ratio of 1560 to 1600 cm in the Raman spectrum. -1 The maximum peak intensity in the range of 1310 to 1350 cm is G. -1When the maximum peak intensity within this range is D, the G / D ratio is preferably 0.5 to 10, more preferably 0.5 to 4.5, and further preferably 0.5 to 2.0.
[0029] The carbon nanotubes preferably have an average outer diameter of 2 to 25 nm, more preferably 5 to 20 nm, and even more preferably 5 to 15 nm. Within the above range, the electrical conductivity and toughness of the carbon nanotubes can be further improved.
[0030] The outer diameter and average outer diameter of carbon nanotubes can be calculated as follows. First, carbon nanotubes are observed and photographed using a transmission electron microscope. Next, 300 carbon nanotubes are randomly selected from the photograph and the outer diameter of each is measured. Next, the average outer diameter (nm) of the carbon nanotubes is calculated as the number average of the outer diameters.
[0031] The volume resistivity of carbon nanotubes is 1.0×10 -2 ~3.0×10 -2 Ω cm is preferred, and 1.0×10 -2 ~2.0×10 -2 It is more preferable that the volume resistivity is Ω·cm. The volume resistivity of the carbon nanotubes can be measured using a powder resistivity measuring device (Loresta GP Powder Resistivity Measuring System MCP-PD-51, manufactured by Nitto Seiko Analytech Co., Ltd.).
[0032] The carbon purity of the carbon nanotube can be determined by a general CHN elemental analysis, and is expressed as the content (mass%) of carbon atoms in the carbon nanotube. The carbon purity is preferably 90 mass% or more, more preferably 95 mass% or more, and even more preferably 98 mass% or more, based on the mass of the carbon nanotube (the mass of the carbon nanotube being 100 mass%). By keeping the carbon purity within the above range, it is possible to prevent problems such as short circuits caused by the formation of dendrites by impurities when used in secondary batteries.
[0033] The amount of metal contained in the carbon nanotube is preferably less than 10% by mass, more preferably less than 5% by mass, and even more preferably less than 2% by mass, based on 100% by mass of the carbon nanotube. Examples of metals contained in the carbon nanotube include metals and metal oxides used as catalysts when synthesizing carbon nanotubes. Specific examples include metals such as cobalt, nickel, aluminum, magnesium, silica, manganese, and molybdenum, metal oxides, and composite oxides thereof.
[0034] The polymer (B) containing a nitrile group-containing structural unit is included in the carbon nanotube dispersion as a dispersant. The dispersant preferably contains the polymer (B) containing a nitrile group-containing structural unit as a main component. For example, the polymer (B) containing a nitrile group-containing structural unit may be 50% by mass or more, 80% by mass or more, 90% by mass or more, or 95% by mass or more based on the total amount of the dispersant, and the dispersant may be entirely the polymer (B) containing a nitrile group-containing structural unit. Since the polymer (B) contains a nitrile group-containing structural unit, it can exhibit excellent flexibility and stability due to its binding strength. Therefore, it can maintain a good conductive network even in an electrode film formed by mixing a carbon nanotube dispersion liquid and a slurry precursor for an electrode film and using the obtained slurry composition for an electrode film.
[0035] In the polymer (B), the nitrile group-containing structural unit is a structural unit containing a nitrile group, preferably a structural unit containing an alkylene structure substituted with a nitrile group, more preferably a structural unit consisting of only an alkylene structure substituted with a nitrile group. The alkylene structure is preferably a linear or branched alkylene structure. The nitrile group-containing structural unit may further contain a structural unit containing (or consisting of) an alkyl structure substituted with a nitrile group. The number of nitrile groups contained in the nitrile group-containing structural unit is preferably one.
[0036] The nitrile group-containing structural unit preferably contains a structural unit represented by the following general formula (1A).
[0037] General formula (1A) [ka]
[0038] In general formula (1A), n represents an integer of 2 or more. n is preferably an integer of 6 or less, more preferably an integer of 4 or less, and even more preferably an integer of 3 or less. In particular, n is preferably 2. In this specification, "*" represents a bond to another structure.
[0039] The nitrile group-containing structural unit preferably contains a structural unit represented by the following general formula (1B).
[0040] General formula (1B) [ka]
[0041] In formula (2B), R represents a hydrogen atom or a methyl group. R is preferably a hydrogen atom.
[0042] The method of introducing the nitrile group-containing structural unit into the polymer (B) is not particularly limited, but a method of preparing a polymer by polymerization reaction using a monomer composition containing a nitrile group-containing monomer is preferred. The finally obtained polymer (B) contains a nitrile group-containing monomer unit as a nitrile group-containing structural unit. Examples of the nitrile group-containing monomer capable of forming the nitrile group-containing structural unit include a monomer containing a polymerizable carbon-carbon double bond and a nitrile group. For example, an α,β-ethylenically unsaturated group-containing compound having a nitrile group can be mentioned, and specifically, acrylonitrile, methacrylonitrile, etc. can be mentioned. In particular, from the viewpoint of increasing the intermolecular force between the polymers (B) and / or between the polymer (B) and the dispersed substance (adsorbed substance), it is preferable that the nitrile group-containing monomer contains acrylonitrile. The nitrile group-containing monomer can be used alone or in combination of two or more kinds.
[0043] The content of the nitrile group-containing structural unit is preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more, based on the mass of the polymer (B) (i.e., when the mass of the polymer (B) is 100% by mass). The content of the nitrile group-containing structural unit is preferably 50% by mass or less, more preferably 46% by mass or less, and even more preferably 40% by mass or less, based on the mass of the polymer (B) (i.e., when the mass of the polymer (B) is 100% by mass). By setting the content of the nitrile group-containing structural unit within the above range, the adsorption to the dispersed material and the affinity to the dispersion medium can be controlled, and the dispersed material can be stably present in the dispersion medium. In addition, the affinity of the polymer (B) to the electrolyte can be controlled, and problems such as the polymer (B) dissolving in the electrolyte in the battery and increasing the resistance of the electrolyte can be prevented.
[0044] Moreover, the polymer (B) preferably contains an aliphatic hydrocarbon structural unit. The aliphatic hydrocarbon structural unit is a structural unit containing an aliphatic hydrocarbon structure, and is preferably a structural unit consisting of only an aliphatic hydrocarbon structure. The aliphatic hydrocarbon structure contains at least a saturated aliphatic hydrocarbon structure, and may further contain an unsaturated aliphatic hydrocarbon structure. The aliphatic hydrocarbon structure preferably contains at least a linear aliphatic hydrocarbon structure, and may further contain a branched aliphatic hydrocarbon structure.
[0045] Examples of the aliphatic hydrocarbon structural unit include an alkylene structural unit, an alkenylene structural unit, an alkyl structural unit, an alkanetriyl structural unit, an alkanetetrayl structural unit, etc. The aliphatic hydrocarbon structural unit preferably contains at least an alkylene structural unit.
[0046] The alkylene structural unit is a structural unit containing an alkylene structure, and is preferably a structural unit consisting of only an alkylene structure. The alkylene structure is preferably a linear alkylene structure or a branched alkylene structure.
[0047] The alkylene structural unit preferably contains a structural unit represented by the following general formula (2A).
[0048] General formula (2A) [ka]
[0049] In general formula (2A), n represents an integer of 1 or more. n is preferably an integer of 2 or more, more preferably an integer of 3 or more, and particularly preferably an integer of 4 or more. n is preferably an integer of 6 or less, and more preferably an integer of 5 or less. In particular, n is preferably 4.
[0050] The alkylene structural unit preferably contains a structural unit represented by the following general formula (2B).
[0051] General formula (2B) [ka]
[0052] In general formula (2B), n represents an integer of 1 or more. n is preferably an integer of 2 or more, and more preferably an integer of 3 or more. n is preferably an integer of 5 or less, and more preferably an integer of 4 or less. In particular, n is preferably 3.
[0053] The alkylene structural unit preferably contains a structural unit represented by the following general formula (2C).
[0054] General formula (2C) [ka]
[0055] In general formula (2C), n represents an integer of 1 or more. n is preferably an integer of 4 or less, more preferably an integer of 3 or less, and even more preferably an integer of 2 or less. In particular, n is preferably 2.
[0056] The method for introducing an aliphatic hydrocarbon structural unit into the polymer (B) is not particularly limited, but examples thereof include the following method (2a) or (2b).
[0057] In the method (2a), a polymer is prepared by polymerization reaction using a monomer composition containing a conjugated diene monomer. The prepared polymer contains a monomer unit derived from the conjugated diene monomer. In the present invention, the "monomer unit derived from the conjugated diene monomer" may be referred to as the "conjugated diene monomer unit", and the monomer unit derived from other monomers may be omitted in the same manner. Next, the conjugated diene monomer unit is hydrogenated to convert at least a part of the conjugated diene monomer unit into an alkylene structural unit. Hereinafter, "hydrogenation" may be referred to as "hydrogenation". The finally obtained polymer (B) contains the unit obtained by hydrogenating the conjugated diene monomer unit as an alkylene structural unit.
[0058] The conjugated diene monomer unit includes at least a monomer unit having one carbon-carbon double bond. For example, the 1,3-butadiene monomer unit, which is a conjugated diene monomer unit, includes at least one monomer unit selected from the group consisting of a monomer unit having a cis-1,4 structure, a monomer unit having a trans-1,4 structure, and a monomer unit having a 1,2 structure, and may include two or more monomer units. The conjugated diene monomer unit may further include a monomer unit having no carbon-carbon double bond and including a branch point. In this specification, the "branch point" refers to a branch point in a branched polymer, and when the conjugated diene monomer unit includes a monomer unit having a branch point, the above prepared polymer and polymer (B) are branched polymers.
[0059] In the method (2b), a polymer is prepared by polymerization reaction using a monomer composition containing an α-olefin monomer. The prepared polymer contains α-olefin monomer units. The finally obtained polymer (B) contains the α-olefin monomer units as alkylene structural units.
[0060] Among these, the method (2a) is preferred because the polymer can be easily produced. The carbon number of the conjugated diene monomer is 4 or more, preferably 4 to 6. Examples of the conjugated diene monomer include conjugated diene compounds such as 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, and 1,3-pentadiene. Among these, 1,3-butadiene is preferred. The alkylene structural unit preferably contains a structural unit (hydrogenated conjugated diene monomer unit) obtained by hydrogenating a conjugated diene monomer unit, and more preferably contains a structural unit (hydrogenated 1,3-butadiene monomer unit) obtained by hydrogenating a 1,3-butadiene monomer unit. The conjugated diene monomer may be used alone or in combination of two or more.
[0061] The hydrogenation is preferably a method capable of selectively hydrogenating conjugated diene monomer units. Examples of the hydrogenation method include known methods such as oil phase hydrogenation and aqueous phase hydrogenation.
[0062] The hydrogenation can be carried out by a conventional method. For example, the hydrogenation can be carried out by treating a polymer having conjugated diene monomer units dissolved in a suitable solvent with hydrogen gas in the presence of a hydrogenation catalyst. Examples of the hydrogenation catalyst include iron, nickel, palladium, platinum, and copper.
[0063] In the method (2b), the carbon number of the α-olefin monomer is 2 or more, preferably 3 or more, and more preferably 4 or more. The carbon number of the α-olefin monomer is preferably 6 or less, and more preferably 5 or less. Examples of the α-olefin monomer include α-olefin compounds such as ethylene, propylene, 1-butene, and 1-hexene. The α-olefin monomer may be used alone or in combination of two or more.
[0064] The alkylene structural unit preferably includes at least one selected from the group consisting of structural units containing a linear alkylene structure and structural units containing a branched alkylene structure, more preferably includes at least one selected from the group consisting of structural units consisting only of linear alkylene structures and structural units consisting only of branched alkylene structures, and further preferably includes at least one selected from the group consisting of structural units represented by the above formula (2B) and structural units represented by the above formula (2C).
[0065] The alkylene structural unit may include a structural unit containing a linear alkylene structure and a structural unit containing a branched alkylene structure. When the alkylene structural unit includes a structural unit containing a linear alkylene structure and a structural unit containing a branched alkylene structure, the content of the branched alkylene structure is preferably 70 mass% or less, more preferably 65 mass% or less, based on the mass of the alkylene structural unit (i.e., when the mass of the alkylene structural unit is 100 mass%). In particular, it is preferably 20 mass% or less, more preferably 18 mass% or less, and even more preferably 15 mass% or less. When the polymer (B) includes a structural unit containing a linear alkylene structure and a structural unit containing a branched alkylene structure, the content of the branched alkylene structure is, for example, 1 mass% or more, may be 5 mass% or more, or may be 10 mass% or more, based on the mass of the alkylene structural unit (i.e., when the mass of the alkylene structural unit is 100 mass%).
[0066] In the aliphatic hydrocarbon structural unit, the content of the alkylene structural unit is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more, based on the total mass of the aliphatic hydrocarbon structural units (i.e., when the mass of the aliphatic hydrocarbon structural units is 100% by mass).The content of the alkylene structural unit is, based on the total mass of the aliphatic hydrocarbon structural units (i.e., when the mass of the aliphatic hydrocarbon structural units is 100% by mass), for example, less than 100% by mass, and may be 99.5% by mass or less, 99% by mass or less, or 98% by mass or less.The content of the alkylene structural unit may be 100% by mass.
[0067] The content of the aliphatic hydrocarbon structural unit is preferably 40% by mass or more, more preferably 50% by mass or more, and even more preferably 60% by mass or more, based on the mass of the polymer (B) (i.e., when the mass of the polymer (B) is 100% by mass). The content of the aliphatic hydrocarbon structural unit is preferably less than 85% by mass, more preferably 75% by mass or less, and even more preferably 70% by mass or less, based on the mass of the polymer (B) (i.e., when the mass of the polymer (B) is 100% by mass).
[0068] Furthermore, the polymer (B) may contain any structural unit. Examples of the structural unit include an amide group-containing structural unit, a carboxyl group-containing structural unit, an alkenylene structural unit, an alkyl structural unit, and a structural unit containing a branch point such as an alkanetriyl structural unit or an alkanetetrayl structural unit. The structural unit containing a branch point is a structural unit different from the structural unit containing a branched alkylene structure and the structural unit containing a branched alkyl structure.
[0069] The amide group-containing structural unit is a structural unit containing an amide group, preferably a structural unit containing an alkylene structure substituted with an amide group, more preferably a structural unit consisting of only an alkylene structure substituted with an amide group. The alkylene structure is preferably a linear or branched alkylene structure. The amide group-containing structural unit may further contain a structural unit containing (or consisting of) an alkyl structure substituted with an amide group. The number of amide groups contained in the amide group-containing structural unit is preferably one.
[0070] The amide group-containing structural unit preferably contains a structural unit represented by the following general formula (3A).
[0071] General formula (3A) [ka]
[0072] In general formula (3A), n represents an integer of 2 or more. n is preferably an integer of 6 or less, more preferably an integer of 4 or less, and even more preferably an integer of 3 or less. In particular, n is preferably 2. R' each independently represents a hydrogen atom or a substituent. The substituent is preferably an alkyl group or a hydroxyalkyl group. It is preferable that at least one R' is a hydrogen atom, and more preferably two R' are hydrogen atoms.
[0073] The amide group-containing structural unit preferably contains a structural unit represented by the following general formula (3B).
[0074] General formula (3B) [ka]
[0075] In the general formula (3B), R represents a hydrogen atom or a methyl group. R is preferably a hydrogen atom. Each R' independently represents a hydrogen atom or a substituent. The substituent is preferably an alkyl group or a hydroxyalkyl group. At least one R' is preferably a hydrogen atom, and more preferably two R's are hydrogen atoms.
[0076] The method of introducing the amide group-containing structural unit into the polymer (B) is not particularly limited, but for example, a polymer can be prepared by polymerization reaction using a monomer composition containing an amide group-containing monomer. The prepared polymer contains the amide group-containing monomer unit. The finally obtained polymer (B) contains the amide group-containing monomer unit as an amide group-containing structural unit.
[0077] Examples of the amide group-containing monomer include monoalkyl (meth)acrylamides such as (meth)acrylamide, N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N-propyl (meth)acrylamide, and N-isopropyl (meth)acrylamide; dialkyl (meth)acrylamides such as N,N-dimethyl (meth)acrylamide and N,N-diethyl (meth)acrylamide; N-(hydroxyalkyl) (meth)acrylamides such as N-(2-hydroxyethyl) (meth)acrylamide, N-(2-hydroxypropyl) (meth)acrylamide, and N-(2-hydroxybutyl) (meth)acrylamide; diacetone (meth)acrylamide; and acryloylmorpholine. In this specification, "(meth)acryl" refers to acryl or methacryl. In particular, the amide group-containing monomer preferably contains at least one selected from the group consisting of acrylamide, methacrylamide, and N,N-dimethylacrylamide. The amide group-containing monomer may be used alone or in combination of two or more.
[0078] The content of the amide group-containing structural unit is preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 3% by mass or less, and particularly preferably 2% by mass or less, based on the mass of the polymer (B) (i.e., when the mass of the polymer (B) is taken as 100% by mass). When the content of the amide group-containing structural unit is within the above range, it is possible to prevent the problem of gelation of the conductive material dispersion during storage, which may occur when the hydrogen bonds between the polymers (B) become too strong.
[0079] The carboxyl group-containing structural unit is a structural unit containing a carboxyl group, preferably a structural unit containing an alkylene structure substituted with a carboxyl group, more preferably a structural unit consisting of only an alkylene structure substituted with a carboxyl group. The alkylene structure is preferably a linear or branched alkylene structure. The carboxyl group-containing structural unit may further contain a structural unit containing (or consisting of) an alkyl structure substituted with a carboxyl group. The number of carboxyl groups contained in the carboxyl group-containing structural unit is preferably one or two. By including a carboxyl group-containing structural unit in the polymer (B), the adsorption force to the dispersed material can be improved, and the viscosity of the conductive material dispersion can be reduced, thereby improving the dispersion efficiency.
[0080] The carboxyl group-containing structural unit preferably contains a structural unit represented by the following general formula (4A).
[0081] General formula (4A) [ka]
[0082] In general formula (4A), n represents an integer of 2 or more. n is preferably an integer of 6 or less, more preferably an integer of 4 or less, and even more preferably an integer of 3 or less. In particular, n is preferably 2.
[0083] The carboxyl group-containing structural unit preferably contains a structural unit represented by the following general formula (4B).
[0084] General formula (4B) [ka]
[0085] In formula (4B), R represents a hydrogen atom or a methyl group. R is preferably a hydrogen atom.
[0086] The method for introducing the carboxyl group-containing structural unit is not particularly limited, but examples thereof include the following method (4a) or (4b).
[0087] In the method (4a), a polymer is prepared by polymerization using a composition containing a carboxyl group-containing monomer. The prepared polymer contains carboxyl group-containing monomer units. The finally obtained polymer (B) contains the carboxyl group-containing monomer units as carboxyl group-containing structural units.
[0088] In the method (4b), a polymer containing an amide group-containing structural unit is first prepared by the method (3a) or the like. Next, the amide group contained in the amide group-containing structural unit is hydrolyzed in an acidic atmosphere to convert the amide group-containing structural unit into a carboxyl group-containing structural unit. The polymer (B) finally obtained contains, as a carboxyl group-containing structural unit, a unit obtained by modifying the amide group contained in the amide group-containing structural unit by hydrolysis.
[0089] In the method (4a), examples of the carboxyl group-containing monomer include unsaturated monocarboxylic acids such as (meth)acrylic acid, crotonic acid, and isocrotonic acid; and unsaturated dicarboxylic acids such as maleic acid, fumaric acid, citraconic acid, mesaconic acid, glutaconic acid, and itaconic acid. In particular, the carboxyl group-containing monomer preferably contains at least one selected from the group consisting of acrylic acid and maleic acid. The carboxyl group-containing monomer may be used alone or in combination of two or more.
[0090] In the method (4b), in order to create an acidic atmosphere, at least one acid selected from the group consisting of inorganic acids and organic acids can be used.
[0091] In the method (4b), examples of inorganic acids include hydrochloric acid, nitric acid, phosphoric acid, sulfuric acid, boric acid, hydrofluoric acid, etc. Examples of organic acids include formic acid, acetic acid, citric acid, oxalic acid, succinic acid, malic acid, benzoic acid, benzenesulfonic acid, etc. Among these, succinic acid and citric acid are preferred.
[0092] In the method (4b), the amount of the acid used is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more, based on the mass of the polymer (B). The amount of the acid used is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less, based on the mass of the polymer (B). If the amount used is too small, modification of the amide group by hydrolysis tends not to occur easily. If the amount used is too large, it may cause corrosion of the dispersion device and / or the inside of the battery.
[0093] The content of the carboxyl group-containing structural unit is preferably less than 1 mass %, more preferably 0.5 mass % or less, and even more preferably 0.3 mass % or less, based on the mass of the polymer (B) (i.e., when the mass of the polymer (B) is 100 mass %). If the content of the carboxyl group-containing structural unit is less than (or less than) the above range, it is possible to prevent the problem of gelation of the conductive material dispersion during storage, which can occur when hydrogen bonds between the polymers (B) become too strong, as described below.
[0094] The alkenylene structural unit is a structural unit containing an alkenylene structure, and is preferably a structural unit consisting of only an alkenylene structure. The alkenylene structure is preferably a linear alkenylene structure or a branched alkenylene structure.
[0095] The alkenylene structural unit preferably includes at least one selected from the group consisting of a structural unit containing a linear alkenylene structure and a structural unit containing a branched alkenylene structure, and more preferably includes at least one selected from the group consisting of a structural unit consisting only of a linear alkenylene structure and a structural unit consisting only of a branched alkenylene structure.
[0096] For example, when the polymer (B) is obtained through the above method (2a), the conjugated diene monomer unit having a carbon-carbon double bond in the unit may remain in the molecule of the polymer (B) without being hydrogenated. The finally obtained polymer (B) may contain the conjugated diene monomer unit having a carbon-carbon double bond in the unit as an alkenylene structural unit.
[0097] The alkyl structural unit is a structural unit containing an alkyl structure (however, it is a structural unit that does not fall under other aliphatic hydrocarbon structural units such as branched alkylene structural units, nitrile group-containing structural units, amide group-containing structural units, and carboxyl group-containing structural units), and is preferably a structural unit consisting of only an alkyl structure. The alkyl structure is preferably a linear alkyl structure or a branched alkyl structure.
[0098] The alkyl structural unit preferably includes at least one type selected from the group consisting of structural units containing a linear alkyl structure and structural units containing a branched alkyl structure, and more preferably includes at least one type selected from the group consisting of structural units consisting only of a linear alkyl structure and structural units consisting only of a branched alkyl structure.
[0099] For example, when the polymer (B) is obtained through the above-mentioned method (2a) or (2b), it is preferable that at least a hydrogenated conjugated diene monomer unit or an α-olefin monomer unit is introduced as a terminal group of the polymer (B). The finally obtained polymer (B) may contain these monomer units as alkyl structural units.
[0100] The alkanetriyl structural unit is a structural unit containing an alkanetriyl structure, and is preferably a structural unit consisting of only an alkanetriyl structure. The alkanetetrayl structural unit is a structural unit containing an alkanetetrayl structure, and is preferably a structural unit consisting of only an alkanetetrayl structure.
[0101] For example, when the polymer (B) is obtained through the above method (2a), the conjugated diene monomer unit may be introduced into the molecule of the polymer (B) as a monomer unit having no carbon-carbon double bond and having a branch point. In this case, the finally obtained polymer (B) is a branched polymer, and may contain the conjugated diene monomer unit as an aliphatic hydrocarbon structural unit having a branch point, such as an alkanetriyl structural unit or an alkanetetrayl structural unit. When the aliphatic hydrocarbon structural unit contains a structural unit having a branch point, the polymer (B) is a branched polymer. The branched polymer may be a network polymer. The polymer (B) containing a structural unit having a branch point can be three-dimensionally adsorbed to the dispersed material, and therefore the dispersibility and stability can be further improved.
[0102] Preferred embodiments of the polymer (B) include the following. A polymer (B) in which the total content of the aliphatic hydrocarbon structural unit and the nitrile group-containing structural unit contained in the polymer (B) is 80 mass% or more and 100 mass% or less based on the mass of the polymer (B). The total content is preferably 90 mass% or more, more preferably 95 mass% or more, and even more preferably 98 mass% or more. A polymer (B) in which the total content of aliphatic hydrocarbon structural units, nitrile group-containing structural units, and amide group-containing structural units contained in the polymer (B) is 80 mass% or more and 100 mass% or less based on the mass of the polymer (B). The total content is preferably 90 mass% or more, more preferably 95 mass% or more, and even more preferably 98 mass% or more. A polymer (B) in which the total content of aliphatic hydrocarbon structural units, nitrile group-containing structural units, amide group-containing structural units, and carboxyl group-containing structural units contained in the polymer (B) is 80 mass% or more and 100 mass% or less based on the mass of the polymer (B). The total content is preferably 90 mass% or more, more preferably 95 mass% or more, and even more preferably 98 mass% or more.
[0103] In this specification, the content of the structural unit can be determined by utilizing the amount of monomer used, NMR (nuclear magnetic resonance) and / or IR (infrared spectroscopy) measurement.
[0104] The polymerization reaction used for preparing the polymer (B) is preferably an emulsion polymerization reaction, and a conventional emulsion polymerization method can be used. The polymerization agents used in the emulsion polymerization, such as emulsifiers (surfactants), polymerization initiators, chelating agents, oxygen scavengers, and molecular weight regulators, can be any of the conventionally known agents, and are not particularly limited. For example, the emulsifiers usually used are anionic emulsifiers or anionic and nonionic emulsifiers.
[0105] Examples of the anionic emulsifier include fatty acid salts such as potassium tallow fatty acid, partially hydrogenated potassium tallow fatty acid, potassium oleate, and sodium oleate; resin acid salts such as potassium rosinate, sodium rosinate, potassium hydrogenated rosinate, and sodium hydrogenated rosinate; and alkylbenzene sulfonate salts such as sodium dodecylbenzene sulfonate. Examples of the nonionic emulsifier include emulsifiers of the Pluronic (registered trademark) type, such as polyethylene glycol ester type, polypropylene glycol ester type, and block copolymers of ethylene oxide and propylene oxide.
[0106] Examples of the polymerization initiator include thermal decomposition initiators such as persulfates, such as potassium persulfate and ammonium persulfate; organic peroxides, such as t-butyl hydroperoxide, cumene hydroperoxide, diisopropylbenzene hydroperoxide, octanoyl peroxide, and 3,5,5-trimethylhexanoyl peroxide; azo compounds, such as azobisisobutyronitrile; and redox initiators consisting of these and a reducing agent, such as divalent iron ions. Among these, redox initiators are preferred. The amount of the initiator used is, for example, in the range of 0.01 to 10% by mass with respect to the total amount of the monomers.
[0107] Examples of the molecular weight regulator include alkyl mercaptans such as octyl mercaptan, nonyl mercaptan, decyl mercaptan, t-dodecyl mercaptan, and 3-mercapto-1,2-propanediol; thioglycolic acid esters such as octyl thioglycolate, nonyl thioglycolate, and 2-ethylhexyl thioglycolate; 2,4-diphenyl-4-methyl-1-pentene, 1-methyl-4-isopropylidene-1-cyclohexene, α-pinene, and β-pinene.
[0108] The emulsion polymerization reaction may be either a continuous or batch type. The polymerization temperature may be either low-temperature or high-temperature polymerization, but is preferably 0 to 60°C, more preferably 20 to 50°C. The method of adding the monomer (lump addition, divided addition, etc.), the polymerization time, the polymerization conversion rate, etc. are not particularly limited. The conversion rate is preferably 85% by mass or more, more preferably 90% by mass or more.
[0109] The weight average molecular weight of the polymer (B) is preferably 5,000 or more, more preferably 10,000 or more, and even more preferably 50,000 or more. The weight average molecular weight of the polymer (B) is preferably 500,000 or less, more preferably 400,000 or less, and even more preferably 300,000 or less. When the weight average molecular weight of the polymer (B) is 5,000 or more and 500,000 or less, the adsorption to the dispersed material and the affinity to the dispersion medium are good, and the stability of the dispersion tends to be improved. In this specification, the weight average molecular weight is a weight average molecular weight in terms of polystyrene, and can be measured by gel permeation chromatography (GPC). Specifically, it may be measured by the method described in the examples.
[0110] Polymer (B) has a Mooney viscosity (ML 1+4 , 100°C) is preferably 100 or less. 1+4 The polymer (B) having a Mooney viscosity (ML 100° C.) of 100 or less can further improve the dispersibility, stability, and handleability of the carbon nanotube dispersion. 1+4 The "temperature (temperature: 100° C., 100° C.)" can be measured at a temperature of 100° C. in accordance with JIS K6300-1. Specifically, it may be measured by the method described in the examples.
[0111] The Mooney viscosity of the polymer (B) is preferably 100 or less, more preferably 70 or less, even more preferably 65 or less, even more preferably 60 or less, and even more preferably 50 or less. If the Mooney viscosity of the polymer (B) is too high, the polymer (B) has a low adsorption force to the carbon fiber surface, and the carbon fiber having a strong cohesive force cannot be dispersed, which may make it difficult to prepare a uniform conductive material dispersion. In addition, since the obtained conductive material dispersion has a high viscosity, it is not possible to efficiently remove metal foreign matter that is mixed in from the raw materials by methods such as iron removal with a magnet, filtration, and centrifugation, and the battery performance may be reduced due to the remaining metal foreign matter.
[0112] The Mooney viscosity of the polymer (B) can be adjusted by the following method, but is not particularly limited thereto. For example, the Mooney viscosity can be adjusted by changing the composition (e.g., structural unit type and content, hydrogenation rate), structure (e.g., linearity rate), molecular weight, preparation conditions (e.g., polymerization temperature, amount of molecular weight regulator) of the polymer (B).
[0113] Preferred embodiments of the polymer (B) include the following. The content of the nitrile group-containing structural unit is from 15% by mass to 50% by mass based on the mass of polymer (B), and the weight average molecular weight of the polymer is from 5,000 to 500,000, more preferably from 10,000 to 400,000. The content of the nitrile group-containing structural unit is 15% by mass or more and 50% by mass or less based on the mass of the polymer (B), the weight average molecular weight of the polymer is 5,000 or more and 500,000 or less, more preferably 10,000 or more and 400,000 or less, and the Mooney viscosity (ML 1+4 , 100℃) is 70 or less.
[0114] The polymer (B) may be any polymer containing a nitrile group-containing structural unit, and may be either a synthetic product or a commercially available product. Examples of commercially available products of the polymer (B) include Therban (registered trademark) 4307 (manufactured by ARLANXEO Co., Ltd., Mooney viscosity (ML 1+4 , 100℃) 70, acrylonitrile content 43.0%), Zetpol (registered trade name) 2000L (manufactured by Zeon Corporation, Mooney viscosity (ML 1+4 , 100°C) 65, acrylonitrile content less than 36.2%.
[0115] The carbon nanotube dispersion may contain other dispersants in addition to the polymer (B). The other dispersants are not particularly limited as long as they can disperse and stabilize the carbon nanotubes, and surfactants, resin-type dispersants, etc. can be used, with resin-type dispersants being preferred.
[0116] Specific examples of the resin-type dispersant include cellulose derivatives (cellulose acetate, cellulose acetate butyrate, cellulose butyrate, cyanoethyl cellulose, ethyl hydroxyethyl cellulose, nitrocellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, and the like, or salts thereof), polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, polyacrylonitrile, poly(meth)acrylic acid, or salts thereof, poly(meth)acrylate, and the like. Polymers in which other substituents have been introduced into a portion of these polymers, modified polymers, and the like may also be used. The resin-type dispersant may be used alone or in combination of two or more kinds. The molecular weight of the resin-type dispersant is preferably 10,000 to 150,000, and more preferably 10,000 to 100,000.
[0117] The solvent of the carbon nanotube dispersion liquid is preferably an amide-based organic solvent. The solvent preferably contains an amide-based organic solvent as a main component. For example, the amide-based organic solvent may be 50 mass %, 80 mass % or more, 90 mass % or more, or 95 mass % or more with respect to the total amount of the dispersion medium solvent, and the solvent may be entirely an amide-based organic solvent. The amide-based organic solvent is preferably a solvent capable of dissolving the polymer (B) containing a nitrile group-containing structural unit, and is preferably a solvent capable of dissolving the polymer (B) containing a nitrile group-containing structural unit when each component is contained in a predetermined amount in the carbon nanotube dispersion liquid.
[0118] Examples of the amide-based organic solvent include N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, and N-methylcaprolactam. The amide-based organic solvent may be used alone or in combination of two or more. In particular, the amide-based organic solvent preferably contains at least one selected from the group consisting of N-methyl-2-pyrrolidone and N-ethyl-2-pyrrolidone, and more preferably contains N-methyl-2-pyrrolidone.
[0119] It is preferable that the carbon nanotube dispersion is substantially free of water. In this specification, substantially free of water means that water is not intentionally added. In the carbon nanotube dispersion, the water content is preferably less than 5% by mass, more preferably less than 1% by mass, based on the mass of the polymer (B) containing a nitrile group-containing structural unit. Water exceeding the allowable amount may cause a decrease in the adsorption of the polymer (B) to the dispersed material, and the dispersed material may not be allowed to exist stably in the dispersion solvent. By setting the water content within the above range, the phenomenon of the carbon nanotube dispersion gelling during storage can be more effectively prevented.
[0120] The solvent for the carbon nanotube dispersion is preferably an amide-based organic solvent that is substantially free of water. The "pH" of a carbon nanotube dispersion that is substantially free of water refers to the value measured using a general pH meter after adding water to the carbon nanotube dispersion so that the solids concentration after adding water is 50% by mass when the solids concentration before adding water is 100% by mass, and can be measured, for example, by the following method.
[0121] While stirring a carbon nanotube dispersion with a solid content concentration of 5% by mass using a disperser, water is added so that the solid content concentration of the carbon nanotube dispersion becomes 2.5% by mass. After stirring uniformly, the pH of the carbon nanotube dispersion can be measured at 25°C using a benchtop pH meter (Seven Compact S220 Expert Pro, manufactured by Mettler Toledo). The carbon nanotube dispersion preferably has a pH of 9.0 or more. The pH of the carbon nanotube dispersion is preferably 9.0 to 14.0, more preferably 9.0 to 13.0. If the pH exceeds the above range, the various raw materials and exterior materials in the battery are likely to corrode, or the binder is likely to gel.
[0122] The pH of the carbon nanotube dispersion can be adjusted by adding a base or by using carbon nanotubes that exhibit basicity. When adjusting the pH by adding a base, at least one base selected from the group consisting of inorganic bases and organic bases can be used as the base to be added.
[0123] Examples of inorganic bases include chlorides, hydroxides, carbonates, nitrates, sulfates, phosphates, tungstates, vanadates, molybdates, niobates, or borates of alkali metals or alkaline earth metals; and ammonium hydroxide. Among these, hydroxides of alkali metals or alkaline earth metals are preferred from the viewpoint of easily supplying cations. Examples of hydroxides of alkali metals include lithium hydroxide, sodium hydroxide, potassium hydroxide, and the like. Examples of hydroxides of alkaline earth metals include calcium hydroxide, magnesium hydroxide, and the like. Among these, it is more preferable to use at least one selected from the group consisting of lithium hydroxide, sodium hydroxide, and potassium hydroxide. The metal contained in the inorganic base may be a transition metal.
[0124] Examples of organic bases include amine compounds such as methylamine, ethylamine, propylamine, butylamine, hexylamine, octylamine, dioctylamine, trioctylamine, aminoethanol, aminopropanol, aminobutanol, and 2-methoxyethylamine. Examples of organic hydroxides include trimethyl-2-hydroxyethylammonium hydroxide, tetramethylammonium hydroxide, cetyltrimethylammonium hydroxide, hexadecyltrimethylammonium hydroxide, trimethylphenylammonium hydroxide, 3-trifluoromethyl-phenyltrimethylammonium hydroxide, and benzyltrimethylammonium hydroxide. The organic hydroxide is a salt containing an organic cation and a hydroxide ion. Among these, it is particularly preferable to use at least one selected from the group consisting of aminoethanol, aminopropanol, trimethyl-2-hydroxyethylammonium hydroxide, and tetramethylammonium hydroxide.
[0125] The content of the base is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more, based on the mass of the polymer (B). The content of the base is preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less, based on the mass of the copolymer. If the amount used is too small, the resulting carbon nanotube dispersion liquid tends to have a high viscosity. If the amount used is too large, the stability of the resulting carbon nanotube dispersion liquid may be poor, and furthermore, it may cause corrosion of the dispersion device and / or the inside of the battery.
[0126] In the carbon nanotube dispersion, the content of the carbon nanotubes (A) is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and may be 1% by mass or more, based on the mass of the carbon nanotube dispersion (based on the mass of the carbon nanotube dispersion being 100% by mass). The content of the carbon nanotubes (A) is preferably 30% by mass or less, more preferably 20% by mass or less, and may be 15% by mass or less or 10% by mass or less, based on the mass of the carbon nanotube dispersion (based on the mass of the carbon nanotube dispersion being 100% by mass). By setting the content of the carbon nanotubes contained in the carbon nanotube dispersion within the above range, the carbon nanotubes can be well and stably present without causing precipitation or gelation. In addition, it is preferable to appropriately adjust the content of the carbon nanotubes so that a carbon nanotube dispersion exhibiting an appropriate viscosity is obtained, taking into account the specific surface area of the carbon nanotubes, affinity to the dispersion medium, and the like.
[0127] For example, from the viewpoint of achieving both good dispersibility and stability, the carbon nanotube content may be 10 mass% or less, and preferably 8 mass% or less, based on the mass of the carbon nanotube dispersion liquid (the mass of the carbon nanotube dispersion liquid being 100 mass%). On the other hand, since the dispersibility and stability of the carbon nanotubes can be improved by the copolymer (B), the carbon nanotube content may be 2 mass% or more, or 5 mass% or more, based on the mass of the carbon nanotube dispersion liquid (the mass of the carbon nanotube dispersion liquid being 100 mass%).
[0128] In the carbon nanotube dispersion, the content of the polymer (B) is preferably 0.1 to 200 parts by mass, more preferably 0.5 to 100 parts by mass, and even more preferably 1.0 to 80 parts by mass, per 100 parts by mass of the carbon nanotubes (A). From the viewpoint of good dispersibility and stability, the content of the polymer (B) is preferably 2 parts by mass or more per 100 parts by mass of the carbon nanotubes (A). Also, from the viewpoint of the conductivity of the dispersion, the content of the polymer (B) is preferably 50 parts by mass or less per 100 parts by mass of the carbon nanotubes (A). In the carbon nanotube dispersion liquid, the content of polymer (B) is not particularly limited based on the mass of the carbon nanotube dispersion liquid (the mass of the carbon nanotube dispersion liquid being 100 mass%), but is preferably 0.01 to 20 mass%, more preferably 0.05 to 10 mass%, and even more preferably 0.1 to 8 mass%. When the carbon nanotube dispersion liquid contains other dispersants in addition to the polymer (B), the total content of the polymer (B) and the other dispersants in the carbon nanotube dispersion liquid is preferably 0.1 to 200 parts by mass, more preferably 0.5 to 100 parts by mass, and even more preferably 1.0 to 80 parts by mass, per 100 parts by mass of the carbon nanotubes (A). When the carbon nanotube dispersion contains other dispersants and other polymer compounds in addition to the polymer (B), the total content of the polymer compounds in the carbon nanotube dispersion is preferably 30 mass % or less, more preferably 20 mass % or less, and even more preferably 15 mass % or less, based on the mass of the carbon nanotube dispersion (mass of the carbon nanotube dispersion being 100 mass %). Furthermore, the carbon nanotube dispersion may be substantially free of other polymer compounds than the polymer (B) and other dispersants. The solid content of the carbon nanotube dispersion liquid is preferably 0.5 to 30 mass %, more preferably 1.0 to 25 mass %, and further preferably 2.0 to 20 mass %.
[0129] The method for producing the carbon nanotube dispersion is not particularly limited. The carbon nanotube dispersion can be obtained, for example, by mixing a dispersant, a solvent, and carbon nanotubes, and dispersing the carbon nanotubes in the solvent. In addition to the dispersant, the solvent, and the carbon nanotubes, any other component may be mixed. Alternatively, the carbon nanotube dispersion can be obtained, for example, by dissolving the dispersant in a solvent, mixing the carbon nanotubes, and dispersing the carbon nanotubes in the solvent. In addition to the dispersant, the solvent, and the carbon nanotubes, any other component such as an additional solvent may be mixed. When mixing a solvent, it is preferable that the solvent is the same as the solvent that dissolves the dispersant. The order of adding the dispersant or the carbon nanotubes to the container is not particularly limited. It is preferable that the dispersant is present together with the carbon nanotubes at any point in the process of dispersing the carbon nanotubes.
[0130] As the dispersing device, a dispersing machine that is generally used for dispersing pigments, etc., can be used. For example, a mixer such as a disperser, a homomixer, or a planetary mixer, a homogenizer (Advanced Digital Sonifer (registered trademark), MODEL 1 manufactured by BRANSON, Examples of media-type dispersers include 450DA, M-Technique's "Clearmix," PRIMIX's "Filmix," Silverson's "Abramix," etc.), paint conditioners (Red Devil), colloid mills (PUC's "PUC Colloid Mill," IKA's "Colloid Mill MK"), cone mills (IKA's "Cone Mill MKO," etc.), ball mills, sand mills (Shinmaru Enterprises' "Dyno Mill," etc.), attritors, pearl mills (Eirich's "DCP Mill," etc.), and Coball mills; high-pressure homogenizers (Genus' "Genus PY," Sugino Machine's "Starburst," Nanomizer's "Nanomizer," etc.); media-less dispersers such as M-Technique's "Clear SS-5" and Nara Kikai's "MICROS," and other roll mills, but are not limited to these.
[0131] For example, in order to promote wetting of the carbon nanotubes and disintegrate coarse particles, it is preferable to use a high shear mixer in the initial dispersion step, and then to use a high pressure homogenizer in order to disperse the carbon nanotubes while maintaining their fiber length. In addition, after dispersing with the high pressure homogenizer, the dispersion state can be made uniform while maintaining the fiber length by further dispersing with a bead mill. The pressure when using the high pressure homogenizer is preferably 60 to 150 MPa, more preferably 60 to 120 MPa.
[0132] Dispersion methods using a dispersing device include batch dispersion, pass dispersion, circulation dispersion, etc., and any of these methods may be used, or two or more methods may be combined. Batch dispersion is a method in which dispersion is performed using only the dispersing device body without using piping or the like. It is easy to handle, so it is preferable for small-scale production. Pass dispersion is a dispersion method in which the dispersing device body is equipped with a tank that supplies the liquid to be dispersed through piping and a tank that receives the liquid to be dispersed, and the liquid is passed through the dispersing device body. In addition, circulation dispersion is a method in which the liquid to be dispersed that has passed through the dispersing device body is returned to the tank that supplies the liquid to be dispersed, and dispersion is performed while circulating. In either case, the longer the processing time, the more the dispersion progresses, so it is sufficient to repeat the pass or circulation until the desired dispersion state is achieved, and the processing amount can be increased by changing the size of the tank or the processing time. Pass dispersion is preferable in that it is easier to uniformize the dispersion state compared to circulation dispersion. Circulation dispersion is preferable in that the work and manufacturing equipment are simple compared to pass dispersion. In the dispersion step, the disintegration of aggregated particles, the loosening, wetting, stabilization, etc. of carbon nanotubes proceed sequentially or simultaneously, and the final dispersion state differs depending on how the steps proceed, so it is preferable to control the dispersion state in each dispersion step by using various evaluation methods. For example, the dispersion state can be controlled by the method described in the Examples.
[0133] The dispersibility of carbon nanotubes in a carbon nanotube dispersion can be indicated by the phase angle and complex modulus measured by dynamic viscoelasticity measurement. The phase angle means the phase shift of the stress wave when the strain applied to the carbon nanotube dispersion is a sine wave. If the material is a pure elastic body, the phase angle will be 0° because the stress wave will be in phase with the applied strain. On the other hand, if the material is a pure viscous body, the stress wave will be 90° advanced. In a typical viscoelasticity measurement sample, the phase angle will be a sine wave greater than 0° and less than 90°, and if the dispersibility of carbon nanotubes in the carbon nanotube dispersion is good, the phase angle will approach 90° for a pure viscous body. In addition, the complex modulus of the carbon nanotube dispersion becomes smaller as the dispersibility of carbon nanotubes is good and the viscosity of the carbon nanotube dispersion becomes lower.
[0134] The phase angle and complex modulus measured by dynamic viscoelasticity measurement generally depend on the concentration of carbon nanotubes in the dispersion. Since carbon nanotubes have a high specific surface area, the lower the carbon nanotube content, the closer the resulting dispersion becomes to a pure viscous body, and the closer the phase angle becomes to 90°. Conversely, it is difficult to uniformly disperse carbon nanotubes in a dispersion containing a high concentration of carbon nanotubes, and the phase angle of the resulting dispersion may be less than 2°. In the present invention, since the copolymer (B) can achieve both good dispersibility and stability, a carbon nanotube dispersion having a phase angle of 2° or more at 25°C and a frequency of 1 Hz can be obtained even when the carbon nanotube concentration is high.
[0135] The complex modulus of the carbon nanotube dispersion at 25°C and a frequency of 1 Hz measured by dynamic viscoelasticity measurement may be less than 120 Pa, more preferably 60 Pa or less, and even more preferably 20 Pa or less. The complex modulus of the carbon nanotube dispersion at 25°C and a frequency of 1 Hz is preferably 0.01 Pa or more, more preferably 0.05 Pa or more, and even more preferably 0.1 Pa or more. The phase angle of the carbon nanotube dispersion at 25°C and a frequency of 1 Hz may be 2° or more, more preferably 5° or more, even more preferably 10° or more, and even more preferably 45° or more. The phase angle at 25°C and a frequency of 1 Hz is preferably 90° or less, more preferably 85° or less, and even more preferably 80° or less. The complex modulus and phase angle of the carbon nanotubes can be evaluated by dynamic viscoelasticity measurement. Specifically, the complex modulus and phase angle can be measured by the method described in the Examples.
[0136] The carbon nanotube dispersion has a small complex modulus because the aggregates of the carbon nanotubes are loosened by the effect of the dispersant containing the polymer (B). In the carbon nanotube dispersion, it is preferable that the carbon nanotube concentration x (mass%) in the carbon nanotube dispersion and the complex modulus y (Pa) of the carbon nanotube dispersion at 25°C and a frequency of 1 Hz as determined by dynamic viscoelasticity measurement satisfy the relationships of the following formulas (1), (2), and (3). y<17x (1) y<120 (2) 0.1≦x≦10 (3)
[0137] That is, from the above formulas (1) and (2), the complex modulus y of the carbon nanotube dispersion liquid measured by dynamic viscoelasticity measurement is preferably less than 120 Pa and satisfies y<17x. Also, from the above formula (3), the carbon nanotube concentration x (mass%) is preferably in the range of 0.1≦x≦10. In formula (2), the complex modulus y may be less than 120 Pa, but is preferably 100 Pa or less, or 50 Pa or less. The complex modulus y is not particularly limited, but may be 0.1 Pa, 0.5 Pa, 1 Pa or more. In formula (3), the carbon nanotube concentration x may be 0.1 mass% or more, but is preferably 0.5 mass% or more, or 1 mass% or more. The carbon nanotube concentration x may be 10 mass% or less, but is preferably 8 mass% or less, or 5 mass% or less.
[0138] The carbon nanotube dispersion is preferably in a state in which no sedimentation or separation of the carbon nanotubes is observed immediately after the dispersion treatment. The carbon nanotube dispersion preferably maintains a dispersed state for a long period of time immediately after the dispersion treatment. Furthermore, the carbon nanotube dispersion is preferably free from gelation for a long period of time, since gelation during storage makes it difficult to redisperse the carbon nanotube dispersion. The dispersibility of the carbon nanotube dispersion can also be evaluated by its viscosity, and the lower the viscosity, the better the dispersibility. From this perspective, the viscosity of the carbon nanotube dispersion is preferably less than 10,000 mPa·s, more preferably less than 5,000 mPa·s, even more preferably less than 2,000 mPa·s, and even more preferably less than 500 mPa·s, as measured at 60 rpm at 25°C using a B-type viscometer. This initial viscosity may be 1 mPa·s or more, 10 mPa·s or more, or 100 mPa·s or more. A specific method for measuring the viscosity is as described in the Examples.
[0139] <Slurry precursor for electrode membrane> The electrode membrane slurry precursor contains an electrode active material (D), a low molecular weight acidic compound (E), a fluoropolymer (F), and an amide-based organic solvent (C').
[0140] The active material (D) is the material that serves as the basis for the battery reaction. The active material is divided into a positive electrode active material and a negative electrode active material based on the electromotive force.
[0141] The positive electrode active material is not particularly limited, but a material capable of reversibly doping or intercalating lithium ions can be used. For example, metal compounds such as metal oxides and metal sulfides can be mentioned. Specifically, oxides of transition metals such as Fe, Co, Ni, Mn, composite oxides with lithium, and inorganic compounds such as transition metal sulfides can be mentioned. Specifically, transition metal oxide powders such as MnO, V2O5, V6O 13 , TiO2, etc.; composite oxide powders of lithium and transition metals such as lithium nickelate, lithium cobaltate, lithium manganate with a layered structure, and lithium manganate with a spinel structure; lithium iron phosphate-based materials which are phosphate compounds with an olivine structure; transition metal sulfide powders such as TiS2 and FeS can be mentioned. The positive electrode active material is preferably a substance containing at least Ni. The positive electrode active material can also be used alone or in combination of two or more.
[0142] As the negative electrode active material, a material capable of reversibly doping or intercalating lithium ions can be used. For example, alloy systems such as metallic Li, its alloys such as tin alloys, silicon alloys, and lead alloys; Li X Fe2O3, Li X Fe3O4, Li X WO2 (x is a number between 0 < x < 1.), metal oxide systems such as lithium titanate, lithium vanadate, and lithium silicate; conductive polymer systems such as polyacetylene and poly-p-phenylene; carbonaceous powders such as artificial graphite and natural graphite such as highly graphitized carbon materials; carbon-based materials such as resin-fired carbon materials can be mentioned. The negative electrode active material can also be used alone or in combination of two or more.
[0143] The low molecular weight acidic compound (E) is preferably a low molecular weight compound that behaves as an acid relative to the active material used. The low molecular weight compound is a compound having a molecular weight of less than 10,000, preferably a compound having a molecular weight of 5,000 or less, 1,000 or less, 500 or less, or 350 or less. More specifically, the molecular weight of the low molecular weight acidic compound (E) is preferably 10 to 1,000, more preferably 30 to 350, even more preferably 40 to 250, and even more preferably 50 to 200. The low molecular weight acidic compound (E) may be either a synthetic product or a commercially available product, and may be used alone or in combination of two or more types.
[0144] In the electrode membrane slurry precursor, when the active material (D) and the fluoropolymer (F) are contained, basic impurities originating from the active material (D) may act on the fluoropolymer (F) and cause gelation of the fluoropolymer (F). Examples of basic impurities include lithium hydroxide remaining in the synthesis process of the active material (D). Adding a low molecular weight acidic compound (E) to the electrode membrane slurry precursor neutralizes the basic impurities and suppresses gelation of the fluoropolymer (F). In addition, the low molecular weight acidic compound (E) may reduce the dispersibility of carbon black when added directly to a composition to which carbon black has been added. However, the low molecular weight acidic compound (E) may be mixed with the active material (D) and the fluoropolymer (F) before being added to the carbon black dispersion, and then mixed with the carbon black dispersion as the electrode membrane slurry precursor to prevent the reduction in dispersibility of carbon black.
[0145] The acid dissociation constant (pKa) of the low molecular weight acidic compound (E) is preferably -5 to 10, more preferably -3 to 9, even more preferably -1 to 7, and particularly preferably 1 to 6. The value of the acid dissociation constant can be obtained from a chemical handbook or the like as a value in an aqueous solution at 25°C. If the acid dissociation constant is too large, the expected effect may not be obtained, whereas if it is too small, corrosion of the production line or care in handling may be required.
[0146] The low molecular weight acidic compound (E) may be either an inorganic acid or an organic acid, or a combination thereof. Examples of the low molecular weight acidic compound (E) include carboxylic acid compounds, oxo acid compounds, hydroxy acid compounds, compounds having a carboxy group, a sulfo group, or a phosphoric acid group, etc. The low molecular weight acidic compound (E) preferably has 1 to 3 acidic groups in one molecule, more preferably 1 to 2. Specific examples of the low molecular weight acidic compound (E) include saturated fatty acids such as acetic acid, propionic acid, caprylic acid, and stearic acid; unsaturated carboxylic acids such as oleic acid and sorbic acid; aromatic carboxylic acids such as benzoic acid, salicylic acid, and phthalic acid; dicarboxylic acids such as oxalic acid, succinic acid, adipic acid, and maleic acid; carboxylic anhydrides such as acetic anhydride, benzoic anhydride, phthalic anhydride, and maleic anhydride; hydroxy acids such as tartaric acid, citric acid, and glyceric acid; aromatic sulfonic acids such as benzenesulfonic acid and toluenesulfonic acid; and inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid. These inorganic and organic acids may have counterions.
[0147] The low molecular weight acidic compound (E) is preferably an organic acid, more preferably a carboxylic acid, an oxo acid, or a hydroxy acid, more specifically, a saturated or unsaturated monocarboxylic acid, a saturated or unsaturated dicarboxylic acid, an aromatic carboxylic acid, a hydroxy acid, or an aromatic sulfonic acid. The low molecular weight acidic compound (E) preferably has a carboxy group, more preferably a saturated or unsaturated monocarboxylic acid, or a saturated or unsaturated dicarboxylic acid, and even more preferably a saturated monocarboxylic acid or a saturated dicarboxylic acid.
[0148] The low molecular weight acidic compound (E) is preferably soluble in the electrode membrane slurry precursor, and more preferably dissolves in an amount of 0.1 part by mass or more per 100 parts by mass of N-methyl-2-pyrrolidone at atmospheric pressure and at 0° C. to 40° C.
[0149] The fluoropolymer (F) is contained in the electrode film slurry precursor as a binder resin. The binder resin is a resin used to bond between materials such as active materials and carbon nanotubes. In this specification, the binder resin is different from the polymer (B). That is, the binder resin is selected from resins other than the polymer (B). The binder resin preferably contains the fluoropolymer (F) as a main component. For example, the fluoropolymer (F) may be 50% by mass or more, 80% by mass or more, 90% by mass or more, or 95% by mass or more based on the total amount of the binder resin, and the binder resin may be entirely the fluoropolymer (F).
[0150] The fluoropolymer (F) is a polymeric compound having fluorine atoms, and is preferably a polymer of a fluorohydrocarbon. Examples of the fluoropolymer (F) include polyvinylidene fluoride, polyvinyl fluoride, polytetrafluoroethylene, polychlorotrifluoroethylene, and ethylene fluoride-propylene copolymer, and may be modified products or copolymers thereof. The fluoropolymer (F) may be used alone or in combination of two or more. Preferably, the fluoropolymer (F) contains polyvinylidene fluoride.
[0151] The weight average molecular weight (Mw) of the fluorine-based polymer (F) is preferably from 10,000 to 2,000,000, more preferably from 100,000 to 1,000,000, and further preferably from 200,000 to 1,000,000.
[0152] The binder resin may contain other binder resins in addition to the fluorine-based polymer (F). Examples of other binder resins include homopolymers or copolymers containing ethylene, propylene, vinyl chloride, vinyl acetate, vinyl alcohol, maleic acid, acrylic acid, acrylic acid esters, methacrylic acid, methacrylic acid esters, acrylonitrile, styrene, vinyl butyral, vinyl acetal, vinyl pyrrolidone, etc. as structural units; polyurethane resins, polyester resins, phenolic resins, epoxy resins, phenoxy resins, urea resins, melamine resins, alkyd resins, acrylic resins, formaldehyde resins, silicone resins; cellulose resins such as carboxymethylcellulose or salts thereof; rubbers such as hydrogenated or non-hydrogenated styrene butadiene rubber and fluororubbers; conductive resins such as polyaniline and polyacetylene. Modified products, copolymers, etc. of these may be used. These may be used alone or in combination of two or more. When used as a binder resin for a slurry composition for a positive electrode membrane, it is preferable to use the fluoropolymer (F) alone from the viewpoint of durability, and it is preferable to use polyvinylidene fluoride as the fluoropolymer (F).When used as a binder resin for a slurry composition for a negative electrode membrane, it is preferable to use, in addition to the fluoropolymer (F), carboxymethylcellulose or a salt thereof, styrene butadiene rubber or a hydrogenated product thereof, polyacrylic acid, etc., which have good adhesion.
[0153] The weight average molecular weight of the binder resin is preferably from 10,000 to 2,000,000, more preferably from 100,000 to 1,000,000, and even more preferably from 200,000 to 1,000,000.
[0154] The solvent of the electrode membrane slurry precursor is preferably an amide-based organic solvent. The solvent preferably contains an amide-based organic solvent as a main component. For example, the amide-based organic solvent may be 50 mass%, 80 mass% or more, 90 mass% or more, or 95 mass% or more of the total amount of the solvent, and the solvent may be entirely an amide-based organic solvent. The details of the amide-based organic solvent are as described above. The electrode membrane slurry precursor preferably does not substantially contain water. The amide-based organic solvent (C) contained in the carbon nanotube dispersion liquid and the amide-based organic solvent (C') contained in the electrode membrane slurry precursor may be the same or different from each other, and when multiple types are contained, all the components may be the same or some or all of the components may be different. Preferably, the amide-based organic solvent (C) contained in the carbon nanotube dispersion liquid and the amide-based organic solvent (C') contained in the electrode membrane slurry precursor may contain the same solvent, and when multiple types are contained, all the components may be the same and in the same ratio.
[0155] In the slurry precursor for an electrode membrane, the active material (D) is preferably 40 to 90 mass %, more preferably 50 to 85 mass %, and even more preferably 60 to 80 mass %, based on the mass of the slurry precursor for an electrode membrane (the mass of the slurry precursor for an electrode membrane being 100 mass %). In the slurry precursor for an electrode membrane, the low molecular weight acidic compound (E) is preferably 0.005 to 2.0 mass %, more preferably 0.01 to 1.0 mass %, and even more preferably 0.02 to 0.5 mass %, based on the mass of the slurry precursor for an electrode membrane (the mass of the slurry precursor for an electrode membrane being 100 mass %). In the slurry precursor for an electrode membrane, the fluoropolymer (F) is preferably 0.1 to 10 mass %, more preferably 0.3 to 8 mass %, and even more preferably 0.5 to 5 mass %, based on the mass of the slurry precursor for an electrode membrane (the mass of the slurry precursor for an electrode membrane being 100 mass %). From the viewpoint of neutralizing basic impurities derived from the active material (D), the amount of the low molecular weight acidic compound (E) is preferably 0.01 to 10 parts by mass, more preferably 0.02 to 5 parts by mass, even more preferably 0.03 to 1 part by mass, and even more preferably 0.05 to 0.5 parts by mass, relative to 100 parts by mass of the active material (D). Furthermore, within these ranges, a decrease in dispersibility of carbon nanotubes due to the action of the low molecular weight acidic compound (E) can be prevented when the electrode membrane slurry precursor is mixed with the carbon nanotube dispersion. The amount of the low molecular weight acidic compound (E) is preferably 1.0 to 30 parts by mass, more preferably 2.0 to 20 parts by mass, and further preferably 3.0 to 10 parts by mass, per 100 parts by mass of the fluoropolymer (F). The amount of the fluoropolymer (F) may be adjusted depending on the composition of the slurry composition for an electrode membrane, but is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 20 parts by mass, and even more preferably 1 to 10 parts by mass, per 100 parts by mass of the active material (D). The solid content of the electrode membrane slurry precursor is preferably 60 to 95 mass %, more preferably 65 to 93 mass %, and further preferably 70 to 90 mass %. The content and solid content of each component of the electrode membrane slurry precursor may be appropriately adjusted according to the content of each component of a desired electrode membrane slurry composition.
[0156] The method for producing the electrode membrane slurry precursor is not particularly limited. The electrode membrane slurry precursor can be obtained, for example, by mixing an active material, a binder resin, a low molecular weight acidic compound, and a solvent, and homogenizing the mixture appropriately. In addition to the active material, the binder resin, the low molecular weight acidic compound, and the solvent, any other components may be mixed. The order in which the active material, the binder resin, and the low molecular weight acidic compound are added to the container is not particularly limited. As a mixing method, various conventionally known methods can be used. In mixing the electrode membrane slurry precursor, for example, a planetary mixer, a rotation-revolution mixer, etc. can be used to uniformly mix the solid contents of the active material (D) and the fluoropolymer (F). The planetary mixer can increase the mixing efficiency by a large shear force by stirring the raw materials with a blade that rotates and revolves around its axis. The rotation-revolution mixer can increase the mixing efficiency by applying a shear force and a centrifugal force to the raw materials by rotating and revolving a container into which the raw materials are charged. Examples of the rotation-revolution mixer include the "Awatori Rentaro" (product name) series manufactured by Thinky Corporation. The electrode membrane slurry precursor may also be mixed using the dispersion device described above for the carbon nanotube dispersion liquid.
[0157] <Slurry Composition> The electrode membrane slurry composition is obtained by mixing a carbon nanotube dispersion liquid and an electrode membrane slurry precursor. Specifically, the electrode membrane slurry composition can include carbon nanotubes (A), a polymer (B) containing a nitrile group-containing structural unit, and an amide-based organic solvent (C), as well as an active material (D), a low-molecular-weight acidic compound (E), a fluorine-based polymer (F), and an amide-based organic solvent (C'). In the electrode membrane slurry composition, if a low molecular weight acidic compound is added later, the stability of the dispersion system is lost, which may cause the composition to thicken or the carbon nanotubes to aggregate. By preparing the carbon nanotube dispersion liquid and the electrode membrane slurry precursor in advance, the dispersibility of the carbon nanotubes is maintained by the polymer (B) in the carbon nanotube dispersion liquid, and by mixing the low molecular weight acidic compound, the fluorine-based polymer, and the active material in the electrode membrane slurry precursor, particularly by allowing the low molecular weight acidic compound and the active material to interact with each other, the carbon nanotubes can maintain good dispersibility and stability even after mixing the carbon nanotube dispersion liquid and the electrode membrane slurry precursor.
[0158] In the slurry composition for an electrode film, the content of the carbon nanotubes (A) is preferably 0.01 to 10 parts by mass, more preferably 0.02 to 5 parts by mass, and further preferably 0.03 to 3 parts by mass, based on 100 parts by mass of the active material. In the slurry composition for an electrode membrane, the content of the fluoropolymer (F) is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 20 parts by mass, and further preferably 1 to 10 parts by mass, relative to 100 parts by mass of the active material.
[0159] In the slurry composition for an electrode film, the content of the polymer (B) may be appropriately adjusted depending on the content of the carbon nanotubes (A), but is preferably 0.01 to 10 parts by mass, and more preferably 0.05 to 5 parts by mass, per 100 parts by mass of the active material. In the slurry composition for an electrode film, the content of the low molecular weight acidic compound (E) may be appropriately adjusted depending on the content of the active material, and is preferably 0.01 to 10 parts by mass, more preferably 0.02 to 5 parts by mass, even more preferably 0.03 to 1 part by mass, and even more preferably 0.05 to 0.5 parts by mass, relative to 100 parts by mass of the active material. The solid content of the slurry composition for an electrode membrane is preferably 30 to 90 mass %, more preferably 30 to 80 mass %, and further preferably 40 to 75 mass %, based on the mass of the slurry composition for an electrode membrane (the mass of the slurry composition for an electrode membrane being 100 mass %).
[0160] In the method for producing the electrode membrane slurry composition, the mixing ratio of the carbon nanotube dispersion liquid and the electrode membrane slurry precursor is not particularly limited, and may be appropriately adjusted so that the components and solid content in the electrode membrane slurry composition are in the above-mentioned content ratio. In addition, a solvent such as an amide-based organic solvent may be further added to adjust the solid content. The electrode membrane slurry composition may further contain other optional components such as wetting agents, antifoaming agents, surfactants, pH adjusters, wetting penetrants, antioxidants, preservatives, antifungal agents, and leveling agents, within the scope of the present invention. The electrode membrane slurry composition may further contain conductive materials other than carbon nanotubes, polymers other than the polymer (B) and the fluoropolymer (F), within the scope of the present invention. These optional components may be added to each composition before mixing the carbon nanotube dispersion and the electrode membrane slurry precursor, or may be added at any timing during or after the mixing process. It is preferable that the active material (D), the low molecular weight acidic compound (E), and the fluoropolymer (F) are not added to the carbon nanotube dispersion before mixing with the electrode membrane slurry precursor. It is also preferable that the carbon nanotubes (A) and the polymer (B) containing a nitrile group-containing structural unit are not added to the electrode membrane slurry precursor before mixing with the carbon nanotube dispersion.
[0161] The electrode membrane slurry can be prepared by mixing the carbon nanotube dispersion liquid and the electrode membrane slurry precursor. As a mixing method, various conventionally known methods can be used. In mixing the electrode membrane slurry, for example, a planetary mixer, a rotation-revolution mixer, etc. can be used to apply a shear force to the slurry to mix each component more uniformly. Examples of the rotation-revolution mixer include the "Awatori Rentaro" (product name) series manufactured by Thinky Corporation. The electrode membrane slurry may be mixed using the dispersion device described above for the carbon nanotube dispersion liquid. The electrode membrane slurry precursor may be added to the carbon nanotube dispersion liquid all at once or in portions, or the electrode membrane slurry precursor may be added to the carbon nanotube dispersion liquid all at once or in portions.
[0162] <Method of manufacturing electrode film> The method for producing an electrode membrane may include, for example, preparing a slurry composition for an electrode membrane and preparing an electrode membrane using the slurry composition for an electrode membrane. The method for preparing the slurry composition for an electrode membrane is as described above.
[0163] The electrode film can be obtained by applying the electrode film slurry composition to a substrate and drying it. A current collector can be used as the substrate. The material and shape of the current collector are not particularly limited, and can be appropriately selected according to various batteries. For example, the material of the current collector can be metal or alloy such as aluminum, copper, nickel, titanium, or stainless steel. In addition, as for the shape, a flat foil is generally used, but a current collector with a roughened surface, a perforated foil current collector, or a mesh current collector can also be used.
[0164] The method of applying the electrode film slurry composition to the current collector is not particularly limited, and any known method can be used.Specific examples include die coating, dip coating, roll coating, doctor coating, knife coating, spray coating, gravure coating, screen printing, and electrostatic painting.The drying method includes, but is not limited to, drying by leaving the electrode film to dry, or drying using a blower dryer, a hot air dryer, an infrared heater, or a far infrared heater.
[0165] After the coating, a rolling treatment may be carried out using a lithographic press, a calendar roll, etc. The thickness of the formed electrode film is, for example, from 1 μm to 500 μm, and preferably from 10 μm to 300 μm.
[0166] <Method of manufacturing battery electrodes> The method for producing a battery electrode may include, for example, preparing a slurry composition for an electrode film, and preparing an electrode film on a current collector using the slurry composition for an electrode film. The method for preparing the slurry composition for an electrode film is as described above. Details of the current collector and the electrode film are as described above.
[0167] <Method of Manufacturing Nonaqueous Electrolyte Secondary Battery> The method for producing a non-aqueous electrolyte secondary battery is, for example, a method for producing a non-aqueous electrolyte secondary battery including a negative electrode, a positive electrode, and an electrolyte, and the step of producing either one of the negative electrode and the positive electrode can include producing a slurry composition for an electrode film, and producing an electrode film on an electrode substrate using the slurry composition for an electrode film. The method for producing the slurry composition for an electrode film is as described above. The details of the current collector and the electrode film are as described above.
[0168] The nonaqueous electrolyte secondary battery includes a positive electrode, a negative electrode, and an electrolyte, and at least one selected from the group consisting of the positive electrode and the negative electrode includes an electrode film formed using the slurry composition for an electrode film obtained by the manufacturing method of one embodiment.
[0169] As the positive electrode, for example, an electrode film prepared by applying a slurry composition for an electrode film containing a positive electrode active material onto a current collector and drying the composition to form a film can be used. As the negative electrode, for example, an electrode film can be used which is prepared by applying a slurry composition for an electrode film containing a negative electrode active material onto a current collector and drying the composition to form a film.
[0170] As the electrolyte, various conventionally known electrolytes capable of moving ions can be used. For example, those containing lithium salts such as LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, Li(CF3SO2)3C, LiI, LiBr, LiCl, LiAlCl, LiHF2, LiSCN, or LiBPh4 (wherein Ph is a phenyl group) can be used, but are not limited thereto. The electrolyte is preferably dissolved in a non-aqueous solvent and used as an electrolytic solution.
[0171] Examples of non-aqueous solvents include, but are not limited to, carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; lactones such as γ-butyrolactone, γ-valerolactone, and γ-octanoic lactone; glymes such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane; esters such as methyl formate, methyl acetate, and methyl propionate; sulfoxides such as dimethyl sulfoxide and sulfolane; and nitriles such as acetonitrile. These solvents may be used alone or in combination of two or more.
[0172] The non-aqueous electrolyte secondary battery may include a separator, such as, but not limited to, a polyethylene nonwoven fabric, a polypropylene nonwoven fabric, a polyamide nonwoven fabric, a porous polyethylene, a porous polypropylene, a porous polyamide, or a material obtained by subjecting these to a hydrophilic treatment.
[0173] The structure of the nonaqueous electrolyte secondary battery is not particularly limited, but typically includes a positive electrode and a negative electrode, and a separator that is provided as necessary, and can be in various shapes according to the purpose of use, such as a paper type, a cylindrical type, a button type, or a laminated type. EXAMPLES
[0174] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples as long as it does not exceed the gist of the present invention. Unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass". In the examples, "polymer (B)" may be referred to as "copolymer" or "dispersant", "carbon nanotube" may be referred to as "CNT", and "N-methyl-2-pyrrolidone" may be referred to as "NMP".
[0175] Table 1 shows the synthesis recipe for polymer (B), Table 2 shows the recipe for the CNT dispersion and the evaluation results thereof, Table 3 shows the relationship between the CNT concentration of the CNT dispersion and the complex modulus of elasticity, Table 4 shows the recipe for the slurry precursor for the electrode film, Tables 5 and 6 show the recipes for the slurry for the electrode film, and Table 7 shows the evaluation results of the positive electrode and the battery.
[0176] <Measurement of weight average molecular weight (Mw) of copolymer> The weight average molecular weight (Mw) of the copolymer was measured by gel permeation chromatography (GPC) equipped with an RI detector. The apparatus used was HLC-8320GPC (manufactured by Tosoh Corporation), and three separation columns were connected in series. The packing materials were "TSK-GEL SUPER AW-4000", "AW-3000", and "AW-2500" manufactured by Tosoh Corporation, respectively. The oven temperature was 40°C, and an N,N-dimethylformamide solution of 30 mM triethylamine and 10 mM LiBr was used as the eluent, and the measurement was performed at a flow rate of 0.6 mL / min. The concentration of the measurement sample was adjusted to 1% using a solvent consisting of the eluent, and 20 microliters were injected. The weight average molecular weight is a polystyrene equivalent value.
[0177] <Mooney viscosity of copolymer (ML 1+4 , 100℃) The Mooney viscosity of a copolymer is measured by preparing a measurement sample from a copolymer solution containing a solvent capable of dissolving it. When the copolymer is dissolved in NMP, the NMP solution of the copolymer is coagulated with water, washed with methanol, and vacuum dried at a temperature of 60°C for 12 hours to prepare a measurement sample. The Mooney viscosity (ML) of 40 g of the measurement sample is measured using an L-type rotor at a temperature of 100°C in accordance with the Japanese Industrial Standard JIS K6300-1. 1+4 , 100℃) were measured.
[0178] <Measurement of initial viscosity of carbon nanotube dispersion> The viscosity value was measured using a Brookfield viscometer ("BL" manufactured by Toki Sangyo Co., Ltd.) at 25°C. The carbon nanotube dispersion was thoroughly stirred with a spatula, and the viscosity was measured immediately at a rotation speed of 60 rpm. The rotors used for the measurements were No. 1 when the viscosity value was less than 100 mPa·s, No. 2 when it was 100 to 500 mPa·s, No. 3 when it was 500 to 2,000 mPa·s, and No. 4 when it was 2,000 to 10,000 mPa·s. The lower the viscosity, the better the dispersibility, and the higher the viscosity, the worse the dispersibility. The carbon nanotube dispersion obtained was judged to have poor dispersibility when it clearly separated or settled. Evaluation criteria ◎: Less than 500 mPa·s (excellent) ○: 500 mPa·s or more and less than 2,000 mPa·s (good) △: 2,000 mPa·s or more and less than 10,000 mPa·s (acceptable) ×: 10,000 mPa·s or more, settling or separation (defective)
[0179] <Measurement of the complex modulus and phase angle of carbon nanotube dispersion> The complex modulus and phase angle of the carbon nanotube dispersion were evaluated by performing dynamic viscoelasticity measurements at 25°C, 1Hz frequency, and strain rates ranging from 0.01% to 5% using a rheometer (RheoStress1 rotational rheometer manufactured by Thermo Fisher Scientific Co., Ltd.) with a cone diameter of 60 mm and 2°. The smaller the complex modulus obtained, the better the dispersibility, and the larger the complex modulus, the worse the dispersibility. In addition, the larger the phase angle obtained, the better the dispersibility, and the smaller the phase angle, the worse the dispersibility. Complex modulus of elasticity criteria ◎: Less than 20 Pa (Excellent) ○: 20 Pa or more but less than 60 Pa (good) △: 60 Pa or more but less than 120 Pa (acceptable) ×: 120Pa or more (defective) Phase angle judgment criteria ◎: 45° or more (excellent) ○: 10° or more and less than 45° (good) △: 2° to less than 5° (acceptable) ×: Less than 2° (bad)
[0180] <Evaluation of Positive Electrode Resistance> The positive electrode composite slurry was applied to a PET film (thickness 100 μm) using an applicator with a gap of 175 μm, and dried in a hot air oven at 70 °C for 10 minutes and in a hot air oven at 120 °C for 15 minutes to obtain a positive electrode film for conductivity evaluation. The surface resistivity (Ω / □) of the positive electrode composite layer was measured using a Loresta GP, MCP-T610 manufactured by Mitsubishi Chemical Analytec Co., Ltd. After the measurement, the volume resistivity (Ω·cm) was obtained by multiplying it by the thickness of the positive electrode composite layer formed on the PET film. The thickness of the positive electrode composite layer was measured at three points in the positive electrode film using a film thickness meter (DIGIMICRO MH-15M manufactured by NIKON Co., Ltd.) to obtain the average value of the positive electrode film, and was calculated as the difference between the average value of the positive electrode film and the film thickness of the PET film. Judgment criteria ◎: The volume resistivity (Ω·cm) of the positive electrode mixture layer is less than 10 (excellent) ◯: The volume resistivity (Ω·cm) of the positive electrode mixture layer is 10 or more and less than 20 (good) ×: The volume resistivity (Ω·cm) of the positive electrode mixture layer is 20 or more (defective)
[0181] <Evaluation of rate characteristics of non-aqueous electrolyte secondary batteries> The non-aqueous electrolyte secondary battery was placed in a constant temperature room at 25°C, and charge / discharge measurements were performed using a charge / discharge device (SM-8, manufactured by Hokuto Denko Corporation). After constant current / constant voltage charging (cut-off current 1mA (0.02C)) was performed at a charge current of 10mA (0.2C) and a charge end voltage of 4.3V, constant current discharging was performed at a discharge current of 10mA (0.2C) and a discharge end voltage of 3V. After repeating this operation three times, constant current / constant voltage charging (cut-off current (1mA (0.02C)) was performed at a charge current of 10mA (0.2C) and a charge end voltage of 4.3V, and constant current discharging was performed at discharge currents of 0.2C and 3C until the discharge end voltage reached 3.0V, and the discharge capacity was calculated for each. The rate characteristic can be expressed by the ratio of the 0.2C discharge capacity to the 3C discharge capacity, as shown in the following formula 1. (Formula 1) Rate characteristic = 3C discharge capacity / 3rd 0.2C discharge capacity × 100 (%) Judgment criteria ◎: Rate characteristics are 80% or more (excellent) ○: Rate characteristics are 60% or more and less than 80% (good) ×: Rate characteristics are less than 60% (bad)
[0182] <Method for evaluating cycle characteristics of non-aqueous electrolyte secondary batteries> The non-aqueous electrolyte secondary battery was placed in a constant temperature room at 25°C, and charge / discharge measurements were performed using a charge / discharge device (SM-8, manufactured by Hokuto Denko Corporation). After constant current / constant voltage charging (cutoff current 2.5mA (0.05C)) was performed with a charge current of 25mA (0.5C) and a charge end voltage of 4.3V, constant current discharging was performed with a discharge current of 25mA (0.5C) and a discharge end voltage of 3V. This operation was repeated 200 times. The cycle characteristics can be expressed as the ratio of the 3rd 0.5C discharge capacity at 25°C to the 200th 0.5C discharge capacity, as shown in the following formula 2. (Formula 2) Cycle characteristics = 3rd 0.5C discharge capacity / 200th 0.5C discharge capacity × 100 (%) Judgment criteria ◎: Cycle characteristics are 85% or more (excellent) ○: Cycle characteristics are 80% or more and less than 85% (good) ×: Cycle characteristics are less than 80% (defective)
[0183] <Preparation of Polymer (B)> (Preparation of Polymer 1) According to the composition shown in Table 1, 30 parts of acrylonitrile (AN), 70 parts of 1,3-butadiene (BD), 3 parts of potassium soap oleate, 0.3 parts of azobisisobutyronitrile, 0.55 parts of t-dodecyl mercaptan (TDM), and 200 parts of ion-exchanged water were added to a stainless steel polymerization reactor. Under a nitrogen atmosphere, polymerization was carried out at 45°C for 20 hours while stirring, and the polymerization was terminated at a conversion rate of 90%. Unreacted monomers were removed by vacuum stripping to obtain an acrylonitrile-conjugated diene rubber latex with a solid content concentration of about 30%. Subsequently, ion-exchanged water was added to the latex to adjust the total solid content concentration to 12%, and the mixture was placed in a 1L autoclave equipped with a stirrer, and dissolved oxygen in the contents was removed by flowing nitrogen gas for 10 minutes. A catalyst solution prepared by dissolving 75 mg of palladium acetate as a hydrogenation catalyst in 180 mL of ion-exchanged water to which 4 times the molar amount of nitric acid relative to palladium was added was added to the autoclave. After replacing the inside of the autoclave with hydrogen gas twice, the contents of the autoclave were heated to 50°C while pressurizing the autoclave with hydrogen gas up to 3 MPa, and a hydrogenation reaction was carried out for 6 hours. Thereafter, the contents were returned to room temperature, the inside of the autoclave was made into a nitrogen atmosphere, and the solid content was dried to recover polymer 1. The hydrogenation rate of polymer 1 was 99.6%, and the weight average molecular weight (Mw) was 150,000. In the acrylonitrile-conjugated diene rubber, the content of the conjugated diene monomer unit was 70% and the content of the nitrile group-containing monomer unit was 30%, based on the mass of the acrylonitrile-conjugated diene rubber. In addition, in Polymer 1, the content of aliphatic hydrocarbon structural units including alkylene structural units was 70%, and the content of nitrile group-containing monomer units was 30%, based on the mass of Polymer 1. The contents of these monomer units and structural units are mass ratios calculated from the amounts of monomers used (hereinafter the same). The Mooney viscosity (ML 1+4 , 100℃) was measured and found to be 50.
[0184] (Preparation of Polymers 2 to 5) The monomer composition to be used was changed according to Table 1, and the content of t-dodecyl mercaptan, which is the molecular weight regulator to be used, was appropriately changed so as to achieve the target Mooney viscosity of the polymer, and Polymers 2 to 5 were prepared. Polymer 5 further contains acrylamide (AAm) in the monomer composition. Other procedures were the same as those for the preparation of Polymer 1 above. The measurement results of the weight average molecular weight and Mooney viscosity of the obtained Polymers 2 to 5 were as shown in Table 1.
[0185] <Preparation of CNT Dispersion> (CNT Dispersion 1) According to the composition shown in Table 2, 94 parts of NMP as an amide-based organic solvent (C) and 1 part of Polymer 1 as a polymer (B) containing a nitrile group-containing structural unit were added to a stainless steel container, and while heating the stainless steel container at 40 °C, it was uniformly stirred with a disper to dissolve Polymer 1. Subsequently, the heating of the stainless steel container was stopped, and while cooling at 25 °C, 100T5 parts of carbon nanotubes (A) were slowly added to the solution while dispersing and stirring, and then batch dispersion treatment was performed with a high shear mixer (manufactured by SILVERSON) equipped with a square hole high sieve until the particle size at the grind gauge became 250 μm or less. Next, the dispersion liquid was supplied from the stainless steel tank to a high-pressure homogenizer (Starburst 10, manufactured by Sugino Machine) through a pipe for additional dispersion treatment. The additional dispersion treatment was performed using a single nozzle chamber, and a 25-pass dispersion treatment was performed at a nozzle diameter of 0.25 mm and a pressure of 100 MPa to obtain CNT Dispersion 1.
[0186] (CNT Dispersion 2 to 5 and CNT Dispersion 10 to 15) CNT Dispersions 2 to 5 and 10 to 15 were obtained in the same manner as CNT Dispersion 1, except that the types and addition amounts of carbon nanotubes (A), polymer (B) containing a nitrile group-containing structural unit, and amide-based organic solvent (C) were changed according to the composition shown in Table 2.
[0187] (CNT Dispersion 6) According to the composition shown in Table 2, 93.8 parts of NMP as an amide-based organic solvent (C) and 1 part of polymer 1 as a polymer (B) containing a nitrile group-containing structural unit were added to a stainless steel container, and the stainless steel container was heated at 40°C while being uniformly stirred with a disperser to dissolve polymer 1. Next, the heating of the stainless steel container was stopped, and while cooling at 25°C, 0.2 parts of ethanolamine were added to the solution as other additives, and 5 parts of 100T as carbon nanotubes (A) were slowly added while being stirred with a disperser, and a batch dispersion treatment was performed using a high shear mixer (manufactured by SILVERSON) equipped with a square hole high shear screen until the particle size on the grind gauge was 250 μm or less. Next, the liquid to be dispersed was supplied from the stainless steel tank to a high pressure homogenizer (Starburst 10, manufactured by Sugino Machine) through a pipe, and an additional dispersion treatment was performed. The additional dispersion treatment was performed using a single nozzle chamber, with a nozzle diameter of 0.25 mm and a pressure of 100 MPa, and 25 passes of dispersion treatment were performed to obtain CNT dispersion liquid 6.
[0188] (CNT dispersions 7 and 9) CNT Dispersions 7 and 9 were obtained in the same manner as CNT Dispersion 6, except that the types and amounts of carbon nanotubes (A), polymer containing a nitrile group-containing structural unit (B), other additives, and amide-based organic solvent (C) were changed according to the composition shown in Table 2.
[0189] (CNT dispersion liquid 8) According to the composition shown in Table 2, 94 parts of NMP as an amide-based organic solvent (C), 0.6 parts of polymer 1 as a polymer (B) containing a nitrile group-containing structural unit, and 0.4 parts of PVP as other additives were added to a stainless steel container, and the stainless steel container was heated at 40°C while stirring uniformly with a disperser to dissolve polymer 1. Next, the heating of the stainless steel container was stopped, and the solution was added while cooling at 25°C, and 5 parts of 100T as carbon nanotubes (A) were slowly added while stirring with a disperser, and a batch-type dispersion treatment was performed using a high-shear mixer (manufactured by SILVERSON) equipped with a square-hole high-shear screen until the particle size on the grind gauge was 250 μm or less. Next, the liquid to be dispersed was supplied from the stainless steel tank to a high-pressure homogenizer (Starburst 10, manufactured by Sugino Machine) through a pipe, and additional dispersion treatment was performed. For the additional dispersion treatment, a single nozzle chamber was used, and 25 passes of dispersion treatment were performed at a nozzle diameter of 0.25 mm and a pressure of 100 MPa to obtain CNT dispersion liquid 8.
[0190] (Comparison CNT dispersion 1) According to the composition shown in Table 2, 94 parts of NMP as an amide-based organic solvent (C) and 1 part of PVP as another additive were added to a stainless steel container, and the stainless steel container was heated at 40°C while being uniformly stirred with a disperser to dissolve the PVP. Next, the heating of the stainless steel container was stopped, and the solution was added while cooling at 25°C, and 5 parts of 100T as carbon nanotubes (A) were slowly added while being stirred with a disperser, and a batch dispersion treatment was performed using a high shear mixer (manufactured by SILVERSON) equipped with a square hole high shear screen until the particle size on the grind gauge was 250 μm or less. Next, the liquid to be dispersed was supplied from the stainless steel tank to a high pressure homogenizer (Starburst 10, manufactured by Sugino Machine) through piping, and additional dispersion treatment was performed. For the additional dispersion treatment, a single nozzle chamber was used, and 25 pass dispersion treatment was performed at a nozzle diameter of 0.25 mm and a pressure of 100 MPa, to obtain a comparative CNT dispersion liquid 1.
[0191] (Comparative CNT dispersion liquid 2) Comparative CNT dispersion 2 was obtained in the same manner as comparative CNT dispersion 1, except that the type and amount of carbon nanotubes (A) and the amount of amide-based organic solvent (C) added were changed according to the composition shown in Table 2.
[0192] The other ingredients used are as follows: Carbon nanotube "100T": K-Nanos 100T (Kumho Petrochemical Co., Ltd., multi-walled CNT, outer diameter 10-15 nm) Carbon nanotube "Flotube9110": Cnano FT9110CNT (manufactured by Cnano Technology Ltd, multi-walled CNT, average outer diameter 11 nm) Carbon nanotube "BT1003M": LUCAN BT1003M (LG Chem Ltd, multi-walled CNT, average outer diameter 13 nm) Carbon nanotube "8A": JENOTUBE8A (manufactured by JEIO Co., Ltd., multi-walled CNT, outer diameter 6-9 nm) Dispersant "HNBR": Zetpol (registered trademark) 2000L (manufactured by Zeon Corporation, Mooney viscosity (ML 1+4 , 100℃) 65, acrylonitrile content 36.2%) Ethanolamine: 2-aminoethanol (Fujifilm Wako Pure Chemical Industries, Ltd.) NaOH: Sodium hydroxide, granular (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) PVP: Polyvinylpyrrolidone ("Polyvinylpyrrolidone K-30" manufactured by Nippon Shokubai Co., Ltd.)
[0193] The initial viscosity, complex modulus and phase angle of the obtained CNT dispersion were evaluated, and the evaluation results are shown in the table.
[0194] CNT dispersions 12 to 15 all use the same carbon nanotubes (8A) and have CNT concentrations of 2.5, 2.0, 1.5, and 1.0 (mass%). The complex modulus [G * ] (Pa) are shown in Table 3. The CNT concentration (mass%) in the dispersion is plotted on the x-axis, and the complex modulus [G* The relationship is shown in the graph in Figure 1, with ] (Pa) on the y-axis.
[0195] 1, it can be confirmed that CNT dispersions 12 to 15 satisfy y<17x. That is, the CNT dispersions of the examples satisfy the relationships of the following formulas (1), (2), and (3). y<17x (1) y<120 (2) 0.1≦x≦10 (3)
[0196] <Preparation of slurry precursor for electrode membrane> (Slurry precursor 1) According to the composition shown in Table 4, 87.03 parts of NMC as the active material (D) and 12.43 parts of a 10% by mass NMP solution of PVDF-1 (containing 1.243 parts of PVDF-1 as solids) as the fluoropolymer (F) were added to a plastic container with a capacity of 150 mL, and then the mixture was stirred at 2,000 rpm for 30 seconds using a centrifugal mixer (Thinky Corporation, Awatori Rentaro, ARE-310). Then, 0.533 parts of a 10% NMP solution of benzoic acid (containing 0.053 parts of benzoic acid as solids) was added as the low molecular weight acidic compound (E), and the mixture was stirred at 2,000 rpm for 20 minutes using a centrifugal mixer to obtain a slurry precursor 1. The solid content of the slurry precursor was 88.33% by mass, and the ratio of the active material (D) and the fluoropolymer (F) was adjusted based on the ratio of the electrode membrane slurry composition (active material (D):fluoropolymer (F):CNT (A) = 98:1.4:0.6). The low molecular weight acidic compound (E) was added so that the ratio of the active material (D):low molecular weight acidic compound (E) was 100:0.061.
[0197] (Slurry precursors 2-9) Slurry precursors 2 to 9 were obtained in the same manner as for slurry precursor 1, except that the types of active material (D), fluoropolymer (F) and low molecular weight acidic compound (E) were changed according to the composition shown in Table 4.
[0198] (Comparative Slurry Precursor 1) According to the composition shown in Table 4, 87.03 parts of NMC as the active material (D) and 12.43 parts of a 10% by mass NMP solution of PVDF-1 (containing 1.243 parts of PVDF-1 as solids) as the fluoropolymer (F) were added to a plastic container with a capacity of 150 mL, and then the mixture was stirred at 2,000 rpm for 30 seconds using a centrifugal mixer (Thinky Corporation, Awatori Rentaro, ARE-310). Next, 0.533 parts of a 10% NMP solution of Isoban-10 (containing 0.053 parts of Isoban-10 as solids) was added as another acidic compound, and the mixture was stirred at 2,000 rpm for 20 minutes using a centrifugal mixer to obtain a comparative slurry precursor 1.
[0199] (Comparative Slurry Precursor 2) Comparative slurry precursor 2 was obtained in the same manner as comparative slurry precursor 1, except that the types of the other acidic compounds were changed according to the composition shown in Table 4.
[0200] The components used are as follows: Active material "NMC": NCM811 (manufactured by Ningbo Ronbay New Energy Technology, composition: LiNi 0.8 Co 0.1 Mn 0.1 O2, 100% solids Active material "NCA": HED (registered trademark) NAT-7050 (manufactured by BASF Toda Battery Materials LLC, composition: LiNi 0.8 Co 0.15 Al 0.05 O2, 100% solids Comparative additive "Isoban-10": Manufactured by Kuraray Co., Ltd., weight average molecular weight 160,000 to 170,000, volatile content ≦4% Comparative additive "polyacrylic acid": Fujifilm Wako Pure Chemical Industries, polyacrylic acid 25,000, molecular weight 25,000 Fluoropolymer "PVDF-1": Polyvinylidene fluoride Kureha KF Polymer W#7300 (manufactured by Kureha Corporation), 100% solids Fluoropolymer "PVDF-2": Polyvinylidene fluoride with polar functional groups Solef#5130 (manufactured by Solvey Co., Ltd.), 100% solids The low molecular weight acidic compounds used were benzoic acid, adipic acid, succinic acid, o-phthalic acid, benzenesulfonic acid, citric acid, and acetic acid, all of which are available from FUJIFILM Wako Pure Chemical Industries, Ltd.
[0201] <Slurry composition for electrode membrane and preparation of electrode membrane> (Example 1-1) According to the formulation shown in Table 5, the CNT dispersion liquid and the electrode membrane slurry precursor were weighed out so that the mass ratio of active material (D): fluoropolymer (F): CNT (A) was 98: 1.4: 0.6, and added to a plastic container with a capacity of 150 mL, and stirred at 2,000 rpm for 30 seconds using a rotation and revolution mixer (Thinky Corporation, Awatori Rentaro, ARE-310) to obtain a slurry composition for electrode membrane. The solid content of the electrode membrane slurry composition was 72 mass%. The obtained electrode film slurry composition was applied to an aluminum foil having a thickness of 20 μm as a current collector using an applicator, and then dried in an electric oven at 120°C ± 5°C for 25 minutes to obtain an electrode with a coating weight per unit area of 20 mg / cm. 2 Further, a rolling process was performed using a roll press (Thank Metal Co., Ltd., 3 t hydraulic roll press) to adjust the density of the electrode layer to 3.1 g / cm. 3 A positive electrode 1a having the above structure was produced.
[0202] (Examples 1-2 to 1-21, Comparative Examples 1-1 to 1-5) Positive electrodes 2a to 21a and comparative positive electrodes 1a to 5a were produced in the same manner as in Example 1-1, except that the types of CNT dispersion liquid and electrode membrane slurry precursor were changed.
[0203] <Preparation of Slurry Composition for Electrode Membrane and Electrode Membrane Not Containing Low-Molecular-Weight Acidic Compound (E)> (Comparative Examples 1-6) According to the recipe shown in Table 6, a slurry composition for electrode membrane was prepared so that the active material (D): fluoropolymer (F): CNT (A) was 98: 1.4: 0.6 in mass ratio. First, CNT dispersion 1 and a 10 mass% NMP solution of PVDF-1 as the fluoropolymer (F) were added to a plastic container with a capacity of 150 mL, and then NMP for adjusting the solid content was added in advance (the amount of NMP added was adjusted so that the solid content of the final slurry composition for electrode membrane was 72%). Then, the mixture was stirred at 2,000 rpm for 30 seconds using a rotation and revolution mixer (Thinky Corporation, Awatori Rentaro, ARE-310) to obtain a binder resin-containing CNT dispersion. Next, NMC was added as the active material (D), and the mixture was stirred at 2,000 rpm for 20 minutes using a rotation and revolution mixer to obtain a slurry composition for electrode membrane. This addition order is referred to as Comparative Procedure 1. The obtained electrode film slurry composition was applied to an aluminum foil having a thickness of 20 μm as a current collector using an applicator, and then dried in an electric oven at 120°C ± 5°C for 25 minutes to obtain an electrode with a coating weight per unit area of 20 mg / cm. 2 Further, a rolling process was performed using a roll press (Thank Metal Co., Ltd., 3 t hydraulic roll press) to adjust the density of the electrode layer to 3.1 g / cm. 3 Thus, a comparative positive electrode 6a was prepared.
[0204] <Preparation of electrode membrane slurry composition and electrode membrane with modified addition procedure> (Comparative Examples 1-7) According to the recipe shown in Table 6, a slurry composition for electrode membrane was prepared so that the active material (D): fluoropolymer (F): CNT (A) was in a mass ratio of 98: 1.4: 0.6. First, CNT dispersion 1 and a 10 mass% NMP solution of PVDF-1 as the fluoropolymer (F) were added to a plastic container with a capacity of 150 mL, and then NMP for adjusting the solid content was added in advance (the amount added was adjusted so that the solid content of the final slurry composition for electrode membrane was 72%). Then, the mixture was stirred at 2,000 rpm for 30 seconds using a rotation and revolution mixer (Thinky Corporation, Awatori Rentaro, ARE-310) to obtain a binder resin-containing CNT dispersion. Next, NMC was added as the active material (D), and the mixture was stirred for 30 seconds at 2,000 rpm using a rotation and revolution mixer. Then, a 10% by mass NMP solution of benzoic acid was added as the low molecular weight acidic compound (E), and the mixture was stirred for 20 minutes at 2,000 rpm using a rotation and revolution mixer to obtain a slurry composition for electrode membranes. The low molecular weight acidic compound (E) was added so that the ratio of the active material (D):low molecular weight acidic compound (E) was 100:0.061. This addition order is referred to as Comparative Procedure 2. The obtained electrode film slurry composition was applied to an aluminum foil having a thickness of 20 μm as a current collector using an applicator, and then dried in an electric oven at 120°C ± 5°C for 25 minutes to obtain an electrode with a coating weight per unit area of 20 mg / cm. 2 Further, a rolling process was performed using a roll press (Thank Metal Co., Ltd., 3 t hydraulic roll press) to adjust the density of the electrode layer to 3.1 g / cm. 3 Thus, a comparative positive electrode 7a was prepared.
[0205] (Comparative Examples 1-8 to 1-13) Comparative positive electrodes 8a to 13a were produced in the same manner as in Comparative Examples 1-7, except that the types of CNT dispersion liquid and electrode membrane slurry precursor were changed according to the formulations shown in Table 6. The resistance of the obtained positive electrode was evaluated, and the results are shown in Table 7.
[0206] <Battery Construction> (Examples 1-1 to 1-21, Comparative Examples 1-1 to 1-13) The standard negative electrode and the positive electrode shown in Tables 5 and 6 below were punched out to 50 mm x 45 mm and 45 mm x 40 mm, respectively, and the separator (porous polypropylene film) inserted between them was inserted into an aluminum laminated bag and dried in an electric oven at 70 ° C for 1 hour. Then, in a glove box filled with argon gas, 2 mL of electrolyte was injected, and the aluminum laminated bag was sealed to prepare batteries 1a to 21a and comparative batteries 1a to 13a. The electrolyte used was a non-aqueous electrolyte prepared by mixing ethylene carbonate, dimethyl carbonate, and diethyl carbonate in a ratio of 1:1:1 (volume ratio) to prepare a mixed solvent, and further adding VC (vinylene carbonate) as an additive to 100 parts of the electrolyte, and then dissolving LiPF6 at a concentration of 1M.
[0207] (Preparation of standard negative electrode) Acetylene black (Denka Black (registered trademark) HS-100, manufactured by Denka Co., Ltd.), CMC, and water were added to a plastic container with a capacity of 150 mL, and the mixture was stirred for 30 seconds at 2,000 rpm using a rotating and revolving mixer (Thinky Corporation, Awatori Rentaro, ARE-310). Artificial graphite was further added as a negative electrode active material, and the mixture was stirred for 150 seconds at 2,000 rpm using a rotating and revolving mixer (Thinky Corporation, Awatori Rentaro, ARE-310). SBR was then added, and the mixture was stirred for 30 seconds at 2,000 rpm using a rotating and revolving mixer (Thinky Corporation, Awatori Rentaro, ARE-310) to obtain a standard negative electrode composite slurry. The solid content of the standard negative electrode composite slurry was 48% by mass. The solid content ratio of the negative electrode active material:conductive material:CMC:SBR in the standard negative electrode mixture slurry was 97:0.5:1:1.5. The abbreviations described above have the following meanings. HS-100: Denka Black HS-100 (manufactured by Denka Co., Ltd., acetylene black, average primary particle diameter 48 nm, specific surface area 39 m 2 / g) Artificial graphite: CGB-20 (manufactured by Nippon Graphite Industries Co., Ltd.), 100% solids CMC: #1190 (manufactured by Daicel FineChem Ltd.), solid content 100% SBR: TRD2001 (JSR Corporation), solid content 48%
[0208] The obtained negative electrode composite slurry was applied to a 20 μm-thick copper foil as a current collector using an applicator, and then dried in an electric oven at 80°C ± 5°C for 25 minutes to obtain an electrode with a coating weight per unit area of 10 mg / cm. 2 Further, a rolling process was performed using a roll press (3 ton hydraulic roll press manufactured by Thank Metal Co., Ltd.) to adjust the density of the negative electrode mixture layer to 1.6 g / cm. 3 Thus, a negative electrode having the above structure was fabricated.
[0209] The rate characteristics and cycle characteristics of the obtained battery were evaluated, and the results are shown in Table 7. As described above, by achieving both dispersibility and stability of carbon nanotubes in the slurry composition for electrode films, a good dispersion state can be maintained in the electrode film to form an efficient conductive network, and a battery with good rate characteristics and cycle characteristics can be manufactured.
[0210] [Table 1]
[0211] [Table 2]
[0212] [Table 3]
[0213] [Table 4]
[0214] [Table 5]
[0215] [Table 6]
[0216] [Table 7]
[0217] Although the present invention has been described with reference to the above-mentioned embodiment, the present invention is not limited to the above-mentioned embodiment. Various modifications that can be understood by those skilled in the art can be made to the configuration and details of the present invention within the scope of the present invention.
Claims
1. a carbon nanotube dispersion liquid including carbon nanotubes (A), a polymer (B) including a nitrile group-containing structural unit, and an amide-based organic solvent (C); preparing an electrode membrane slurry precursor containing an active material (D), a low molecular weight acidic compound (E) having a molecular weight of less than 10,000, a fluorine-based polymer (F), and an amide-based organic solvent (C'); and A method for producing a slurry composition for an electrode membrane, comprising mixing the carbon nanotube dispersion liquid and the electrode membrane slurry precursor.
2. 2. The method for producing a slurry composition for an electrode membrane according to claim 1, wherein the content of the nitrile group-containing structural unit in the polymer (B) containing the nitrile group-containing structural unit is 15 mass% or more and 50 mass% or less based on the mass of the polymer (B).
3. 3. The method for producing a slurry composition for an electrode membrane according to claim 1, wherein the polymer (B) containing a nitrile group-containing structural unit has a weight average molecular weight of 5,000 or more and 500,000 or less.
4. 4. The method for producing a slurry composition for an electrode film according to claim 1, wherein in the carbon nanotube dispersion, a carbon nanotube concentration x (mass%) and a complex modulus y (Pa) of the carbon nanotube dispersion at 25°C and a frequency of 1 Hz as determined by dynamic viscoelasticity measurement satisfy the relationships of the following formulas (1), (2), and (3). y < 17x (1) y < 120 (2) 0.1≦x≦10 (3)
5. A method for producing an electrode membrane, comprising: preparing a slurry composition for an electrode membrane by the production method according to claim 1 ; and producing an electrode membrane by using the slurry composition for an electrode membrane.
6. A method for producing an electrode for a battery, comprising: preparing a slurry composition for an electrode film by the production method according to any one of claims 1 to 4; and producing an electrode film on a current collector using the slurry composition for an electrode film.
7. 5. A method for manufacturing a non-aqueous electrolyte secondary battery including a negative electrode, a positive electrode, and an electrolyte, wherein a step of manufacturing one of the negative electrode and the positive electrode includes preparing a slurry composition for an electrode film by the manufacturing method according to claim 1, and manufacturing an electrode film on a current collector using the slurry composition for an electrode film.
Citation Information
Patent Citations
Positive electrode slurry and application thereof in battery
CN111525137A
Carbon nanotube dispersion and its use
JP2021050106A
Binder composition for electrochemical elements, conductive material dispersion for electrochemical elements, slurry for electrodes for electrochemical elements, electrodes for electrochemical elements, and electrochemical elements
JP6870772B1
Semiconductor laser output controlling method for multi-beam magneto-optical pickup
JP1989013242A
Carbon nanotube-dispersed polar organic solvent and method for producing the same
JP2005162877A